Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Postharvest biocontrol potential and mechanisms of Fusarium tricinctum against pear black spot caused by Alternaria alternata - Yun-Feng Liu; Zheng-Yu Zhu; Na Liu; Bo-Lin Li; Xue-Li He; Yu-Xing Zhang (Postharvest Biology and Technology, 2026)

Step-by-step strategy of electron utilization by binary cocatalysts: Coupling electron-reservoir MoS2 with proton-reduction cobaloxime for enhanced photocatalytic hydrogen evolution - Jianguo He; Lin Chen; Jiahui Yang; Qiongqiong Wang; Hongli Zhang; Keying Lin; Wei Wang; Dong Feng; Baojun Ma (Fuel, 2026)

Ecosystem-specific controls of denitrifier gene abundance and community composition on potential nitrous oxide emissions in upland and paddy soils - Xianchu Su; Guiping Ye; Hang-Wei Hu; Mengmeng Feng; Luyuan Sun; Yuheng Cheng; Zi-Yang He; Jia Liu; Yongxin Lin (Soil Ecology Letters, 2026)

Metagenomic indications of potential pathogen-associated and antibiotic resistance risks following UV–chlorine disinfection in sprout production - Yufei Wei; Lin Zhu; Xiangfu Jin; Huangli Yao; Shanshan He; Pu Feng; Feihong Yu; Yulu Xiang; Zhiheng Li; Shanying He (Environmental Pollution, 2026)

An LLM-based framework with multi-scale temporal disentangling and scale-wise learnable prompt alignment for influent ammonia nitrogen forecasting - Zhixin Li; Danxia Li; Jinrong He; Zhirui Niu; Zheng Liu; Zhihua Feng; Caiyan Lin (Journal of Water Process Engineering, 2026)

Hydroclimatic trend and millennial abruptions in southwestern China since the last deglaciation - Yan Yang; Hai Xu; Jing Wang; Ye Yang; Yunping Song; Jin Zhang; Siwei Shi; Yanpeng Li; Lin Shi; Kaiyang He; Yu Feng; Sheng Xu (Global and Planetary Change, 2026)

Corrigendum to “flexible chain-engineered conjugated polymers with phosphonic acid anchors for synergistic photocatalysis-adsorption uranium extraction” [Chem. Eng. J. 521 (2025) 166451] - Yuanping Jiang; Feng Wang; Junshuo An; Xingfang Yu; Menghan Cao; Guohang He; Danning Xu; Jiajian Yang; Kai Zhang; Yunxiu Zhang; Lin Xu; Zuojia Li; et al. (Chemical Engineering Journal, 2026)

Oral self-assembled nanomedicine orchestrates hierarchical regulation of the lipid–ROS–inflammation cascade for comprehensive therapy of non-alcoholic fatty liver disease - Jia-Jian Zhang; Yin-Sheng Tan; Chen-Lei Zhang; Yan Gui; Fan-Zhi Yan; Jie Hou; Xiang-Xuan Liu; Hua Kong; Meng-Ru Guo; Yang-Feng Cui; Xian-He Lin; Tao-Tao Fan; et al. (Chemical Engineering Journal, 2026)

Size-resolved airborne particle control in a dental operatory: field comparison of window opening, portable air purifier, and UV air disinfection - Chen Chen; Di Zhang; Xiaoyi Xiao; Chuanhao Wang; Ruixin Nie; Xiaojing Lin; Mengmeng Cao; Meiqiu Hong; Yanjun Su; Bin Zhao; Shanshan Shi; Mingyao Yao; et al. (Building and Environment, 2026)

PepOSX-AI: CPP - an interpretable transformer-based deep learning model for prediction of cell-penetrating peptides - Haowen Chen; Weiwei He; Kaiyan Feng; Rong Xu; Sheng Yin; Lin Zheng; Jing Chen; Mouming Zhao; Jucai Xu; Lijun You (Analytica Chimica Acta, 2026)

Causal inference reveals the dominant role of climate-adaptation coupling in future potato production - Zhihao He; Tengcong Jiang; Lin Zhu; Ning Yao; Yi Li; Hao Feng; De Li Liu; Liang He; Jianqiang He; Qiang Yu (Agricultural Systems, 2026)

Sex-specific expression of detoxification proteins contributes to differential metabolic detoxification capacity and acaricide sensitivity in female and male Tetranychus cinnabarinus (Boisduval) - Sihan Chen; Weiwei Sun; Jiayan Duan; Ya Yang; Zhixin Jiang; Mingpeng Wang; Zhifeng Xu; Lin He; Kaiyang Feng (Pesticide Biochemistry and Physiology, 2026)

Ternary synergistic activation of municipal waste incineration bottom ash for high-performance supplementary cementitious materials: Mechanisms, heavy metal immobilization, and sustainability - Jianwen Xiao; Hongxia Qiao; Minggang Shang; Lexiang Nie; Wenhao He; Feng Cao; Gangliang Lin (Environmental Research, 2026)

Dopamine-functionalized gel for rapid iodine and triiodide capture through adsorption-conversion pathway in aqueous media - Xinxin Li; Lin Jiang; Feng Lin; Zikang He; Rongzhi Tang; Yu Tan (Chemical Engineering Journal, 2026)

Artificial dissolved organic matter regulates soil metabolism to optimize wheat productivity: Linking rhizosphere microbial shifts and molecular metabolic pathways - Yahui Ji; Chuanxi Wang; Junjie Lin; Bingyu Wang; Shiying He; Guodong Fang; Lisha Wang; Yuanyuan Feng; Yanfang Feng; Lihong Xue; Zhenyu Wang; Baoshan Xing (Chemical Engineering Journal, 2026)

Integrated multi-omics analysis reveals mechanism of metabolic reprogramming enabling bacterial selenite detoxification and selenium nanoparticles biogenesis by Serratia marcescens HBQT - Yidong Zhang; Jin Lin; Mingyang He; Shiyao Li; Yan Liu; Hao Feng; Yawen Geng; Tao Li; Li Zhang; Jintao Xia; Taohong Zhou (Bioresource Technology, 2026)

Unveiling the Impact of Copper Metabolism on Epithelial-Mesenchymal Transition of Triple-Negative Breast Cancer: Identification of Therapeutic Targets - Kai Zhuang; Lin Yan; Muhammad Waqas; Haixin Feng; Siqi Tang; Haoqi He; Xinshi Yu; Yanling Wang; Zunnan Huang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Genomic landscape of idiopathic male infertility and the pregnancy outcomes following assisted reproductive technology - Chen Tan; Tongyao Hu; Lanlan Meng; King Kin Lam; Qing Zhang; Xilin Xu; Shimin Yuan; Yurong Wang; Zilan Huang; Keren Zhou; Yong Li; Chunbo Xie; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Corrigendum to “Catechol-induced assembly to enhance the performance of antimicrobial peptide fully” [Chem. Eng. J. Volume 524 (2025) 169195] - Xiao Wang; Yuanyuan He; Beibei Cui; Yuan Feng; Jingjing Lin; Xirui Long; Yanchao Wang; Zhen Li; Feng Luo; Jiehua Li; Hong Tan (Chemical Engineering Journal, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

Land-use-driven terrestrial inputs and fresh-seawater mixing jointly shape sediment organic nitrogen in the Pearl River Estuary - Jia Yang; Pengju Li; Yunchao Wu; Jinlong Li; Feng Ye; Yuanbi Yi; Shicheng Lin; Ling Zhang; Zhijian Jiang; Songlin Liu; Xiaoping Huang; Ding He (Science China Earth Sciences, 2026)

Rockburst mitigation by microwave destressing in a deep drill-and-blast tunnel: thermal–damage–stress evolution with a slotted-wall coaxial applicator - Yuntan Ao; Xia-Ting Feng; Shiping Li; Xiaojun Zhang; Juan He; Tianyang Tong; Yifan Zhang; Feng Lin (Tunnelling and Underground Space Technology, 2026)

Undescribed triterpenoid ellagitannins from Castanopsis calathiformis and their potential antiproliferative and hypoglycemic activity - Ya-feng Wang; Ying-rong Bao; Rui-jie He; Nao Pang; Zhang-bin Liu; Bing-yuan Yang; Gui-qin Li; Yong-lin Huang (Phytochemistry, 2026)

High-performance formaldehyde sensing of room-temperature UV-activated Mn-TiO2: Key effects of different crystal phase structures and Mn doping on carrier behavior and adsorption - Yunhong Zhao; Siyuan Guo; Xiao Feng; ZhiHan He; Tengfeng Xie; Ziheng Li; Yanhong Lin (Environmental Research, 2026)

Engineering over-oxidized cu on CNTs for sensitive non-enzymatic glucose sensing and energy applications - Songxin Zhong; Rida Li; Hui Chen; Chao Xiao; Yining Lan; Qi-an Chen; Jian Li; Changqiang Feng; Shizhan Li; Hengchan Qi; Chi Gong; Zukun He; et al. (Chemical Engineering Journal, 2026)

Spontaneous plastome mutations in variegated plants occur predominantly in genes related to transcription and photosynthesis - Zhuoqiao Qiu; Boya Yi; Huajing Feng; Qi Zeng; Peishan Zou; Xirong Zheng; Jianzhong Ni; Manmei He; Ruiying Wang; Shuaixi Zhou; Kainan Ma; Shiou Yih Lee; et al. (Planta, 2026)

Analyzing Muscle Contraction Dynamics Through Continuous Vector Segmentation and Tracking - Wenze Wu; Wenyu Chen; Liuhe Li; Junnan Feng; Zhe Liu; Wei Gu; Lin Gao; Jiankang He; Dichen Li (Annals of Biomedical Engineering, 2026)

Effect of Excavation Sequence and Bolt Support on Surrounding-Rock Stability of a Double-Tunnel System in Jointed Rock Mass - Feng Jiang; Tian-lin Huang; Hai-zhen Huang; Ji-song Wang; Peng He; Gang Wang; Chun-gui Li; Ting-fang Liu; Cheng-cheng Zheng; Zhi-yong Xiao (Applied Geophysics, 2026)

Building tailorable Kagome lattices with quantum-confined orbitals in periodic mirror twin boundaries - Ruo-Han Zhang; Jiang-Hui Pan; Ya-Xin Zhao; Chen-Yue Hao; Ke Lv; Mo-Han Zhang; Xiao-Ya Wang; Ya-Ning Ren; Ji Feng; Lin He (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Deciphering the spatial patterns of a springtime microbial community: Structure, function, and key drivers in the Southern Yellow Sea - Yang Yuan; Wei He; Long Jiang; Lin-Qiong Wang; Xian-Pu Ji; Dao-Feng Zhang; Wen-Jun Li (Journal of Environmental Sciences, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Cadmium isotope systematics in seep carbonates: Constraints on depth-dependent partitioning and paleoenvironmental implications - Qiaohui Zhong; Zice Jia; Lu Yin; Chifeng He; Zhiyong Lin; Xudong Wang; Qianyong Liang; Dong Feng; Jie Li (Chemical Geology, 2026)

Targeting perivascular adipose tissue in vascular aging: innovative translational strategies for disease prevention and monitoring - Peng-Xin Wang; Sha-Qi He; Bei Huang; Zi-Fei Liu; Feng Xu; Jun-Jie Yang; Sai Lu; Hui-Xiang Chen; Ze-Qiang Cai; Ling-Qing Yuan; Xiao Lin (Apoptosis, 2026)

Genetic regulation of insulin resistance surrogate index (TyG) and susceptibility to common diseases based on phenome-wide association study - Jia-Xin Wu; Ling-Huan Bu; Pei He; Ming-Hui Xia; Lin Bo; Fei-Yan Deng; Shu-Feng Lei (Molecular and Cellular Biochemistry, 2026)

Genetic analysis and reproductive interventions in families affected by congenital cataracts: a study of 107 cases - Yun-hao Li; Qi Wang; Yao Peng; Juan Du; Liang Hu; Zhen-hua Tan; Feng Gu; Hao Hu; Qian-jun Zhang; Ge Lin; Guang-xiu Lu; Yue-Qiu Tan; et al. (Journal of Applied Genetics, 2026)

Two new diterpenoid alkaloids from Aconitum legendrei Hand.-Mazz - Ming-Lu Zheng; Feng-Tai Qiu; Qing Tang; Lin Chen; Qin He; Shuai Huang; Xian-Li Zhou (Natural Product Research, 2026)

Biocontrol of tobacco bacterial wilt by Bacillus velezensis Y19: insights into chemotaxis, competition and antagonism - Yajie Hu; Xiaolan Yang; Huiping Wu; Qunling Li; Guangxiong Xiao; Feng Wu; Feng Li; Zihua He; Xiaoxing Lin; Ting Ding (Physiological and Molecular Plant Pathology, 2026)

Lithium isotope fractionation in LCT pegmatite systems: a density functional theory study - He-Feng Lin; Wen-Bin Zhu; Hai-Zhen Wei; Xi-Sheng Xu; Zhi-Qin Xu; M.R. Palmer; Shuang Chen; Jing Ma; Yin-Chuan Li; Da-Sheng Zuo; Ke Yang (Geochimica et Cosmochimica Acta, 2026)

Environmental airflow promotes sweet taste formation in white tea: Insights from metabolomic, transcriptomic and microstructure - Jiao Feng; Junyang Wu; Kailong Liu; Shuping Ye; Kexin Lin; Linling He; Xiangxiang Huang; Dongliang Qiu; Wei Wang; Zhilong Hao (Food Chemistry, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Functional analysis of inducible choline/carboxylesterase CCE01 associated with fenpropathrin and abamectin detoxification in Tetranychus urticae (Koch) - Jinhang Li; Wenxin Cai; Liting Wang; Junfeng He; Yifan Meng; Jingui Liu; Lin Xu; Kaiyang Feng; Guangmao Shen; Peng Wei; Lin He (Pesticide Biochemistry and Physiology, 2026)

Fe(II)/Periodate moderate oxidation as a sustainable strategy for Microcystis aeruginosa inactivation and cyanotoxin mitigation - Shuai Zhang; Shihan Tan; Chenlei Xie; Qiulan Lin; Xiping Feng; Han Zhang; Yunfei He; Jiafeng Ding (Journal of Water Process Engineering, 2026)

Plant diversity shifts soil phosphorus and nitrogen limitations to carbon processes along latitudinal gradients: Role of nutrient stoichiometry - Belayneh Azene; Wenjie Bao; Chaoying Yang; Awoke Guadie; Yalemzewd Nigussie; Min Cao; Kun Xu; Yun Deng; Hua Huang; Guanghong Cao; Feng Liu; Shangwen Xia; et al. (Forest Ecology and Management, 2026)

Cation-anion synergistic interactions in ion-regulated cholesteric liquid crystal Hydroxypropyl methylcellulose coatings for lithium metal batteries - Zhanpeng Du; Yun Huang; Fengliang Wang; Lei Zhang; Jing Tao; Jin Bao; Heguo Zeng; Jiajun He; Huihui Li; Chao Zou; Chunmei Feng; Bingshu Guo; et al. (Chemical Engineering Journal, 2026)

Coupled Effects of Reservoir Level Fluctuations and Rainfall on Landslide Deformation Using InSAR and DEM Analysis - Liu Tie-biao; Liu Ming-quan; Luo Shi-lin; He Kun-lin; Yan Guang-zhi; Chen Guo-feng; Cao Su-ting (Geotechnical and Geological Engineering, 2026)

Agroforestry balances plant–soil–microbe–enzyme interactions and improves its connectivity and homeostasis: Evidence from C:N:P stoichiometric networks - Qi-Wen Xu; Meng-Die Feng; Tian-Yang Li; Lin Xiong; Bo-Yu Ren; Yan-Zheng He; Bing-Hui He (Agriculture, Ecosystems & Environment, 2026)

Anoikis-Related Genes Can Accurately Predict the Occurrence of Endometriosis: A Retrospective Cohort Study via Machine Learning Analysis - Lin Hong; Lan Zheng; Yu-Feng He; Ya-Xing Fang; Hui Chen; Kang-Jia Chen; Shu-Guang Zhou (Biochemical Genetics, 2026)
Endometriosis is one of the most common benign gynecological disorders, characterized by persistent pain and challenges with fertility. Anoikis, a specific form of apoptosis, occurs when cells detach from the extracellular matrix. Recent researches have revealed that anoikis resistance is the most important prerequisite for endometriosis development, but it's still not entirely apparent, yet, what part anoikis plays in endometriosis pathogenesis. We obtained the GSE141549 dataset from the GEO database, which served as our training cohort. Anoikis-related genes (ANRGs), sourced from the GeneCards database, were integrated with differentially expressed genes (DEGs) identified in GSE141549. Consequently, we obtained a collection of differentially expressed anoikis-related genes (DE-ANRGs). Subsequently, we employed machine learning algorithms to screen for key diagnostic DE-ANRGs and developed a nomogram model to predict and diagnose endometriosis. Ultimately, we validated our findings through in vitro experiments and an online endometriosis database. Within the training cohort, a total of 47 DE-ANRGs were identified. Furthermore, three machine learning methods pinpointed four diagnostic genes (CAV1, PDK4, CSPG4, SERPINE1). Based on these genes, we constructed a nomogram to facilitate the prediction and clinical diagnosis of endometriosis. To assess model's predictive accuracy, clinical adaptability, and discriminative ability. We performed calibration curves, Receiver Operating Characteristic curves and decision curve analysis. All assessments demonstrated our model's outstanding performance. Ultimately, consistent expression trends of four genes were observed in GSE7305 test cohort, clinical specimens, and the Turku database when compared to the training cohort. In addition, we also have revealed the immune landscape differences, which may offer new promising immunotherapeutic targets for endometriosis patients in the future. In addition to offering novel perspectives on the role of anoikis in endometriosis pathogenesis, our analysis also identified a panel of distinctive biomarkers with significant diagnostic potential. Graphical abstract

The GATA3-RFPL3-ASK1 axis suppresses breast cancer growth and lung metastasis - Kang Li; Chang Liu; Jun-Hui Yin; Yu-Ting He; Zhi-Zhi Xu; Wen-Jing Zhang; Jian-Qi Wang; Lu-Yao Hou; Jing Feng; Le-Min Lin; Xiu-Qing Duan; Yi Zhou; et al. (Apoptosis, 2026)

Magnetoelastomer-based grain flow sensor for combine harvesters - Xin-Dong Ni; Mao-Lin Li; Fang-Lei Li; Zi-Xuan Dai; Chun-Xiao Xing; Feng Wang; Yan-Xin Yin; Du Chen; Zhi-Zhu He (Computers and Electronics in Agriculture, 2026)

Breaking the trade-off: Trichoderma effector Tahfb1 dual-targets growth and defense pathways via Hsp70L - Yaping Yin; Yuhang Fu; He Wu; Liping Feng; Lijuan He; Runmao Lin; Rui Wang; Zhengbin Tang; Baoping Zhu; Jumei Hou; Jing Zhao; Tong Liu (Pesticide Biochemistry and Physiology, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Sex-specific associations between exposure to metal mixtures and mitochondrial DNA copy number: A repeated-measures study - Junxiu He; Xiaoting Ge; Sencai Lin; Yu Bao; Hong Cheng; Sihan Hu; Xiuming Feng; Qinghua Fan; Ying Yang; Xiaobo Yang (Journal of Environmental Sciences, 2026)

Engineered bacterial extracellular vesicles drive anti-tumor immunity via dendritic cell maturation and trafficking - Zihao Ou; Qianbei Li; Bonan Pan; Junjie Feng; Xiaojing He; Yuanyuan Wu; Yudi Wang; Zhen Cai; Jinduan Lin; Lei Zheng (Chemical Engineering Journal, 2026)

Antioxidant capability of peanut shell extracts obtained using an ethanol–ammonium sulfate two-phase system - Yung-Sheng Lin; Cheng-Kun He; Yun-En Jian; Ming-Ren Chen; Tz-Feng Lin; Cheng-You Chen; Wei-Hsun Wang (Biomass and Bioenergy, 2026)

Boron and oxygen isotopes fractionation between borate minerals and fluids and implications for borate deposit formation - Da-Sheng Zuo; Hai-Zhen Wei; Jian-Jun Lu; M.R. Palmer; A.E. Williams-Jones; Jun-Lin Wang; Shao-Yong Jiang; Ke Yang; He-Feng Lin; Simon V. Hohl; Yi-Chu Chen (Applied Geochemistry, 2026)

Dietary fraxetin modulates the gut-immune axis to alleviate DSS-induced enteritis in grass carp (Ctenopharyngodon idella) - Jie Zhang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; He-Qun Shi; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2026)

Enhancing coastal resilience with nature-based solutions: Policy-driven restoration of a high-energy beach (Changle Airport Beach, China) - Shasha Liu; Fan Yu; Feng Cai; Heshan Lin; Degang Jiang; Patryk Sitkiewicz; Yanyu He; Hang Yin; Michael Wagreich; Ivica Vilibić (Ocean & Coastal Management, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Modeling the evolution of water-environment-economy coupling system with the impacts of inter-basin water transfer project - Danni Jia; Jingwen Zhang; Zejun Li; Maoyuan Feng; Kairong Lin; Xiaohong Chen; Xiaohui Lei; Lixin He; Chao Ma; Jingru Ji (Journal of Hydrology, 2026)

The bioaccumulation characteristics and combined toxicity effects of aged microplastics with adsorbed Hg(II) in oysters - Lianghong Li; Chun Lv; Qijia Zhou; Qiaoguo Tan; Haiying Lin; Qingge Feng; Xiaohong Song; Xianghua Wu; Qiuyan Hu; Lixin Huang; Jie He; Guanjian He; et al. (Journal of Hazardous Materials, 2026)

Microbial mechanisms of arbuscular mycorrhizal fungi in mitigating nitrous oxide emissions via regulating nitrogen metabolism in constructed wetlands - Xiang-Long He; Liang-Cheng Lin; Yi-Hao Li; Yu-Quan Zhong; Hao Xu; Jing-Wen Li; Can Liu; Jun-Feng Wang (Chemical Engineering Journal, 2026)

The promises and risks of carbon-based nanomaterials: a critical review on their roles in soil health and ecosystem safety - Yumeng Song; Wei Lin; Williamson Gustave; Yanchun Zhang; Dongmei Feng; Xiaokai Zhang; Feng He (Environmental Geochemistry and Health, 2026)

Development of a Sensitive Real‐Time PCR Method for Detection of Carp Oedema Virus - Huilin He; Ruixue Feng; Siyi Guo; Bing Han; Jinshan Huang; Xu Lin; Jiyuan Yin; Defeng Zhang; Min Liu; Wen Shi (Journal of Fish Diseases, 2026)
Carp oedema virus disease (CEVD), caused by the carp oedema virus (CEV), results in significant economic losses to the common carp and koi aquaculture industry. The CEVD symptoms resemble those of koi herpesvirus (KHV) and include lethargy, swollen gills, sunken eyes, and skin haemorrhages. Consequently, the development of efficient detection methods is imperative for the prevention and diagnosis of CEVD. In this study, we developed a quantitative real‐time PCR assay for the sensitive detection of CEV infection. Specific primers were designed based on a highly conserved region within the CEV p4a gene. The assay exhibited a sensitivity that was 100‐fold greater than that of the conventional PCR technique, with high specificity, and no observed cross‐reactivity with infectious haematopoietic necrosis virus (IHNV), infectious pancreatic necrosis virus (IPNV), spring viremia of carp virus (SVCV), salmonid alphavirus (SAV), or KHV. Inter‐ and intra‐assay experiments also confirmed the method's high repeatability. In a clinical setting, it showed higher sensitivity compared to the diagnostic methods for CEVD developed by the Center for Environment, Fisheries and Aquaculture Science (CEFAS), while also significantly reducing detection costs. Consequently, the established assay could provide robust technical support for the clinical diagnosis and epidemiological investigation of CEVD.

ER stress disrupts MFN2-related mitophagy via HRD1-PINK1/ parkin axis in bovine embryos - Shu-Ming Shi; Li-Ying Liu; Zhi-Chao Chi; Lin-Yi Qu; Jing-Hang Li; Guan-Lin Jia; Yu-Yan He; Yong-Xun Jin; Ming-Jun Zhang; Xian-Feng Yu (Theriogenology, 2026)

Closing the phosphorus loop: Turning aquaculture wastewater into slow-release fertilizer with an amine-modified wood fiber - Ni Yang; Lisha Wang; Yahui Ji; Yuanyuan Feng; Bingyu Wang; Lin Shi; Lihong Xue; Shiying He; Chen Ling; Yanfang Feng; Baoshan Xing (Chemical Engineering Journal, 2026)

Enhancing pearl luster by targeted delivery of astaxanthin using submicron hollow ordered mesoporous silica to the mantle of pearl oysters - Yuan-shuai Fu; Xi-ke Li; Yue Lin; Yun-ao Li; Yong Zhao; Wei-hao Wu; He Wang; Xue-feng Lv; Yuan Zhang; Yong-heng Zhu; Zhi-yi Bai (Chemical Engineering Journal, 2026)

Base-free oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid boosted by Ru-Na synergy in Ru/Na-Y zeolite catalysts - Lin Li; Chao Feng; Haimei Xu; Ping He; Qisong Yi; Junxiang Jiang; Lu Lin; Jin Hou; Yuanshuai Liu (Chemical Engineering Journal, 2026)

Seasonal variations in greenhouse gas production in coastal sandy sediments - Hao Zheng; Yanqing Feng; Yanshu Wang; Chenqingfeng Gao; Daochao Xing; Zhengyuan Li; Huizhong He; Qiang Liu; Zhengxin Yin; Xianbiao Lin (Marine Pollution Bulletin, 2025)

Divergent impacts of partial manure substitution on soil nitrous oxide emissions dependent on phosphorus availability - Yuheng Cheng; Jinbo Zhang; Hang-Wei Hu; Xiangyin Ni; Jianbo Fan; Song Wan; Mengmeng Feng; Christoph Müller; Ji-Zheng He; Yongxin Lin (Soil Biology and Biochemistry, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

High-efficiency photocatalytic NO removal enabled by dual-ligand modulated assembly of photosensitive TCPP on defective NH2-UiO-66 - Youzhou He; Shuying Gong; Pengfei Zhu; Lijie Zhou; Ning Li; Lin Chen; Xiaoli Xiong; Li Wen; Chenghua Zhang; Yongcheng Feng; Bowen Lei; Xingyan Liu (Journal of Environmental Chemical Engineering, 2025)

Milkfat influences thermal tolerance and biofilm formation of Salmonella Typhimurium during pasteurization - Ziqi Liu; Yuechong Liu; Jian He; Xiaoyan Pei; Yixin Lin; Marciane Magnani; Donghong Liu; Tian Ding; Jinsong Feng (Food Research International, 2025)

Seismic performance of a low yield point steel link with corrugated web for RC double-column bridge bent - Sidong Feng; Jun He; Wei Fan; Weiwei Lin; George Vasdravellis (Engineering Structures, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Phase transformation toughening behaviors of t-ZrO2 nanoparticles in glass sealing of YSZ ceramic and Crofer22H stainless steel for solid oxide fuel cell - Wei Cong; Yangfan Fu; Peng He; Tiesong Lin; Guangjie Feng; Zhanpeng Zhang; Wenlong Duan; Yifeng Wang; Qian Wang (Chemical Engineering Journal, 2025)

Factors influencing soil carbon stocks in secondary subtropical forests of eastern China - Hong Lin; Zaihua He; Kai Tian; Xiangshi Kong; Zhaohui Li; Feng Zhou; Xingjun Tian (CATENA, 2025)

Chemical Ecological Risk Assessment for Aquatic Life Under Climate Change: A Review from Occurrence, Bioaccumulation, and Toxicity Perspective - Wanyu He; Cuihong Chen; Lanpeng Yang; Zhongzhi Chen; Lin Zhu; Lingyan Zhu; Jianfeng Feng (Reviews of Environmental Contamination and Toxicology, 2025)

Inhibitory effect of carvacrol nanoemulsions on Staphylococcus aureus and its biofilms - Yifei Wang; Feng Chen; Zongxin Lu; Lin Ye; Xiaobo Yang; Josphat Njenga Gichure; Joanna Trafiałek; Shuo Zhang; Shoukui He (Journal of Consumer Protection and Food Safety, 2025)

Latitudinal Beta‐Diversity Gradient of Riverine Macroinvertebrate: Interplays of Climatic and Land Use Factors - Ruxia Qiao; Hanrui Wang; Yuqing Lin; Qiuwen Chen; Jianyun Zhang; Kai Chen; Tao Feng; Shufeng He; Hanlu Yan (Global Ecology and Biogeography, 2025)
Aim Climate change and land use have major effects on macroinvertebrate biodiversity, but it is unclear how they shape spatial variations, particularly at large scales. This study explored the latitudinal patterns of beta diversity in riverine macroinvertebrate assemblages and examined how they are shaped by climate and land use. Location China (18°–48° N). Time Period From 2006 and 2021. Major Taxa Studied Riverine macroinvertebrates. Method A comprehensive dataset covering macroinvertebrate taxa from 42 watersheds across China was compiled to explore the latitudinal patterns of taxonomic, functional, and phylogenetic beta diversities, including turnover and nestedness components. Generalised additive models were used to assess the impacts of climatic and land use variables, selected from 20 climatic and 10 land use candidates, on latitudinal patterns of beta diversity. Results Taxonomic and functional beta diversities shared a non‐monotonic latitudinal pattern, minimised at 24°–30° N, contrasting with the monotonic increase in phylogenetic beta diversity. Taxonomic beta diversity was dichotomously regulated by climatic stability and land use: diminishing nestedness in low‐latitude regions while augmenting spatial turnover in high‐latitude regions as latitude increased. For functional beta diversity, climate was identified as an indirect factor influencing historical trait‐pool constraints, whereas land use was identified as a direct factor altering its nestedness component. Phylogenetic beta diversity demonstrated no significant association with contemporary environmental variables. Main Conclusions This study uncovers three facets of macroinvertebrate beta diversity with different latitudinal patterns, highlighting the disparate influences played by climate and land use on these spatial differences as well as the distinct importance of processes causing nestedness and turnover. These insights provide a foundation for latitude‐specific conservation strategies that aim at preserving the macroinvertebrate diversity in rivers.

Salidroside improves bovine embryo quality by mitigating oxidative stress and regulating mitochondrial lipid metabolism - Li-Ying Liu; Xian-Feng Yu; Zhi-Chao Chi; Shu-Ming Shi; Tian Lan; Jia-Hui Leng; Jing-hang Li; Yu-Yan He; Lin-Yi Qu; Guan-Lin Jia; Ilkeun Kong; Ming-Jun Zhang; et al. (Theriogenology, 2025)

Structural insight into GPR155-mediated cholesterol sensing and signal transduction - Delin Li; Xiaokang Zhang; Jie Feng; Yufeng Xie; Pu Han; Ming He; Lin Hao; Tianling Guo; Xiaoyi Bai; Kai Yuan; Junqing Sun; Xuefei Pang; et al. (Science Bulletin, 2025)

Microbiomics and machine learning-assisted approaches reveal amino acid patterns in high-temperature Daqu - Chao Fang; Gailing Shi; Qing He; Shuang Xing; Peng Chen; Feng Shi; Zhiguo Liu; Ping Tang; Liangcai Lin; Cuiying Zhang (Food Chemistry, 2025)

A dynamic prediction model for maximum lateral displacement of foundation pit enclosure structure using multi-source fusion method - He Wei Kuang; Zhi Yong Ai; Gan Lin Gu; Hong Wei Huang; Zeng Zhi Qian; Da Xing Zhou; Yu Xin Zhai; Hai Feng Guo (Computers and Geotechnics, 2025)

Catechol-induced assembly to enhance the performance of antimicrobial peptide fully - Xiao Wang; Yuanyuan He; Beibei Cui; Yuan Feng; Jingjing Lin; Xirui Long; Yanchao Wang; Zhen Li; Feng Luo; Jiehua Li; Hong Tan (Chemical Engineering Journal, 2025)

Synergistic Co single-atom/nanoparticle catalysis enables stable hydrogenation of levulinic acid to gamma-valerolactone with formic acid - He Huang; Wei Zhang; Jianrong Zeng; Mengke Liu; Han Lin; Liwen Mu; Xin Feng; Xiaohua Lu; Lilong Zhang; Jiahua Zhu (Chemical Engineering Journal, 2025)

Magnetic biochar-mediated iron reduction synergizes with microbial co-metabolism for enhanced adsorption and in-situ degradation of sulfamethoxazole - Shujuan Liu; Ning Wang; Yao Li; Dandan Liang; Weihua He; Nan Lin; Jiannan Li; Yujie Feng (Chemical Engineering Journal, 2025)

Identification and semi-quantification of alkylated polycyclic aromatic hydrocarbons in PM2.5 filter samples using in-injection port thermal desorption coupled with two-dimensional gas chromatography and rapid-scanning quadrupole mass spectrometry (TD-GC×GC-qMS) - Manfei Lin; Yongming Feng; Xiao He; Bin-Yu Kuang; X.H. Hilda Huang; Yongmei Liang; Jian Zhen Yu (Atmospheric Pollution Research, 2025)

Deep learning-based species identification of gymnosperm xylem: The practice in digital forestry - Chang Zheng; Tuo He; Lichao Jiao; Yang Lu; Shoujia Liu; Tianxiao Li; Yuanyuan Miao; Dejun Feng; Jian Lin; Xian Feng; Zhonghua Huang; Min Yu; et al. (Computers and Electronics in Agriculture, 2025)

Maintaining high levels of HIF-1α protects osteoarthritis cartilage by activating autophagy - Xiaolei Chen; Gangning Feng; Lufei Shao; Xue Lin; Xiaoxin He; Yong Yang; Xin Zhao; Jiangbo Yan; Long Ma; Yong Zhou; Kuanmin Tian; Hui Wang; et al. (Tissue and Cell, 2025)

Hybrid prediction model for multi-step wastewater influent quality using adaptive wavelet denoising and enhanced Informer - Lili Ma; Danxia Li; Jinrong He; Zhirui Niu; Zheng Liu; Zhihua Feng; Caiyan Lin (Journal of Water Process Engineering, 2025)

Synergistic quorum quenching to the diffusible signal factor and AHLs mediated quorum sensing in Thiothrix controlling filamentous sludge bulking - Rui Liu; Lin Feng; Jie Li; Zhuo-Li Yan; Jian-Hong He; Yue Zhi; Xiao-Wei Xu; Peng Yan; You-Peng Chen (Journal of Environmental Chemical Engineering, 2025)

Helium isotopes in hot springs of the Karakorum fault and the Central Pamir: Tracing mantle contributions and tectonic dynamics - Shuai Wang; Shihua Qi; Xuelian Huang; Boyuan Zhao; Feng Chen; Genyi He; Sijia Wang; Jingyu Lin (Global and Planetary Change, 2025)

Target-tailored PAN membrane for synchronous removal of emulsions and trace Hg(II) from complex aqueous systems: performance and interfacial mechanism study - Jie He; Haiying Lin; Qingge Feng; Xianghua Wu; Jiatong Lv; Qiuyan Hu; Lixin Huang; Guanjian He; Yujiang Fan; Chun Lv (Chemical Engineering Journal, 2025)

A small amount of Pd promotes CO2 adsorption and reduces carbon deposition to double the stability of NiFePd/MgAlO catalyst for plasma-assisted dry reforming reaction - Lian-He Zhao; Shu-Juan Lin; Jian-Feng Diao; Ming-Sheng Wang; Jing Sun; Zhong-Ning Xu; Guo-Cong Guo (Chemical Engineering Journal, 2025)

Flexible chain-engineered conjugated polymers with phosphonic acid anchors for synergistic photocatalysis-adsorption uranium extraction - Yuanping Jiang; Feng Wang; Junshuo An; Xingfang Yu; Menghan Cao; Guohang He; Danning Xu; Jiajian Yang; Kai Zhang; Yunxiu Zhang; Lin Xu; Zuojia Li; et al. (Chemical Engineering Journal, 2025)

Constructing Ni2P/CoP heterojunction with stable built-in electric field to boost overall water splitting at industrial current density - Tian Lin; Huimin Yang; Jianguo Dong; Chunmei Ni; Xuena Gao; Jing Li; Ju Wang; Xiaoyan He; Wenyi Tan; Ligang Feng; Zhao Li (Fuel, 2025)

Enhancing high-temperature phase stability and thermal properties of 5RE(TaxNb1-x)O4 high-entropy ceramics through chemical bonding strength optimization - Mengdi Gan; Liping Lai; Xiaoyu Chong; Qianqian Jin; Wei Yu; Jiankun Wang; Jun Wang; Lin Chen; Jingjin He; Jing Feng (Chemical Engineering Journal, 2025)

Unprecedented triterpenes with anti-inflammatory activity from Limax maximus - Ya-feng Wang; Pei-de Tang; Rui-jie He; Zhang-bin Liu; Yong-qiong Wei; Jun Ruan; Bing-yuan Yang; Yong-lin Huang (Journal of Natural Medicines, 2025)

Seismic scattered wave direct imaging in shallow underground space with undulating surface - Ke Shi; Feng Xu; Zong-ling Yan; He-jun Chai; Xue-ming Jia; Xing-lin Lu; Xian-xin Liu; You-ping Mao (Applied Geophysics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

SMART-assisted discovery of butenolides from the marine-derived Aspergillus sp. NBU4698 with multidrug resistance reversing and anti-inflammatory activity - Hang Zhao; Zhiyan Zhou; Fangjian Feng; Wei Yuan; Lixin Chen; C. Benjamin Naman; Zhiran Ju; Ziyi Zhou; Wenhan Lin; Shan He; Lijian Ding (Phytochemistry, 2025)

Synthesis and characterization of geopolymer microspheres at H3PO4 activated metakaolin and adsorption-immobilization performance of F− - Lin Shao; Hongyang Wei; Huiye Lei; Xingyong Xue; Liu He; Feng Gao; Kaituo Wang (Journal of Cleaner Production, 2025)

Polymeric immunoglobulin receptor (pIgR) in cancer progression: a critical role and potential therapeutic target - Shaoju Qian; Yeqing He; Ruixue Li; Panpan Sun; Xingyi Zhang; Lin Pan; Zhishan Xu; Zhiwei Feng; Rong Lian; Lili Yu (Apoptosis, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Formation and evolution of overpressure and its control on hydrocarbon accumulation in the Yinggehai Basin - Lu Yang; Lin Hu; Gaowei Hu; Yazhen Zhang; Jinqiang Tian; Fang Hao; Zonglin He; Yue Xue; Xuezhe Li; Ziqi Feng; Chunlei Li; Baibing Yang (Science China Earth Sciences, 2025)

Near-complete recovery of phosphorus from fresh human urine: Combining magnesium-air fuel cells with modified granular attapulgite - Lin-Jiang Zhong; Lin-Feng He; Hao-Ran Yang; Shu-Jie Hu; Di Wu; Meng-Yue Zhang; Ying Chen; Xuan Zhao; Hong Liu; Yuan Liu (Journal of Environmental Management, 2025)

Milk peptides alleviate irritable bowel syndrome by suppressing colonic mast cell activation and prostaglandin E2 production in mice - Yu Zhang; Zhiqing Lin; Qi Yao; Jian He; Haotian Feng; Wenyi Zhang; Zhigang Liu; Tian Yuan; Xuebo Liu; Long Ding (Food Research International, 2025)

Formation of aroma characteristics driven by microorganisms during long-term storage of Liubao tea - Chang Xu; Jinming Zhang; Yani Pan; Xinyu Feng; Anran Yan; Xinxin Wang; Lin Xiang; Haowei Guo; Lixin He; Tianyuan Chen; Fangyuan Fan; Shuying Gong; et al. (Food Chemistry, 2025)

Mechanisms underlying the effect of high-temperature curing treatments on the browning response of fresh-cut yams - Xi Pang; Zixin Lin; Mina Wang; Huafeng Liang; Yaqi Zhao; Ying Li; BangJin Yan; Yiyi He; Xianxin Wu; Qing Wang; Bihong Feng (Food Chemistry, 2025)

Artificial Intelligence Seismic Permeability Prediction Method Based on High-Dimensional Petrophysical Template - Hui Long; Xiao-yue Zhou; Yan-xiao He; Hao Hu; Xiao-feng Dai; Lin Jiang (Applied Geophysics, 2025)

Dual pathways of carbon neutrality in urban green spaces: assessment and regulatory strategies - Yuan Feng; Chenyu Fang; Xiaoli Jia; Peihao Song; Lin Zhou; Xin Xu; Kun Wang; Ruizhen He; Nan Guo; Shidong Ge (Sustainable Cities and Society, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

CYP321F3 mediates metabolic resistance to methoxyfenozide in rice stem borer, Chilo suppressalis - Fang-Rui Guo; Shu-Chao Wang; Yan Liu; Shuai Wang; Jing-Mei Huang; Hao Sun; Lin-Feng He; Yuan Xie; Song-Tao Qiao; Feng-Xia Yang; Chris Bass; Cong-Fen Gao; et al. (Pesticide Biochemistry and Physiology, 2025)

Enhancing antibiotic removal in constructed wetlands: A MgFe-LDHs-based strategy for optimizing microbial communities and metabolic functions - Yu-Quan Zhong; Xiang-Long He; Yi-Hao Li; Hui Zhu; Jing-Wen Li; Hao Xu; Can Liu; Liang-Cheng Lin; Jun-Feng Wang (Journal of Hazardous Materials, 2025)

Highly efficient degradation of perfluoroalkyl substances (PFAS) by a novel polytetrafluoroetylene piezocatalyst - Shan Yao; Jieying Lin; Shaoxiong He; Yang Bai; Mingge Jin; Feng Zhu; Jingyun Fang; Mengye Wang (Journal of Hazardous Materials, 2025)

Enhancement of Oryzanol application by constructing modified β-CD inclusion complex and polycaprolactone-chitosan electrospun fiber membranes: Perspectives on wound dressings and grape preservation - Wen Li; Jintao He; Qijue Chen; Feng Bao; Yinqiang Huo; Jing Deng; Qinlu Lin; Feijun Luo (Food Chemistry, 2025)

“Three-birds, one-stone” biomimetic nanozyme system based on oxygen vacancy structure-regulated cascade reaction for inflammatory bowel disease - Tianliang Li; Zhaoming Wang; Zhijie Wang; Yihuan Pu; Lixing Lin; Zeyu Li; Lifei Chen; Xinting Liu; Bin Cao; Yingying Chen; Zhenzhen Li; Zixuan He; et al. (Chemical Engineering Journal, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Identification of a novel strain of carp edema virus affecting Songpu mirror carp in Liaoning, China - Wen Shi; Bing Han; Huilin He; Ruixue Feng; Siyi Guo; Xuanyu Ren; Jinshan Huang; Xu Lin; Jiyuan Yin; Xiaonan Lv; Min Liu (Aquaculture, 2025)

Albaillellarian (radiolaria) assemblages across the Guadalupian–Lopingian boundary (Permian) and their environmental implications - Lei Zhang; Shan Chang; Xia Wang; Marie-Béatrice Forel; Qing-Lai Feng; Wei-Hong He; Taniel Danelian; Martial Caridroit; Qian Liu; Xing-Lin Li (Palaeoworld, 2025)

Human Amniotic Epithelial Stem Cells Promote Functional Recovery After Spinal Cord Injury In Rats By Regulating The Polarization Of Macrophages - Hongyan Zhang; Jingjing Liu; Beike Chen; Xin Chen; Shijun Wei; Guanghui Zhang; Xiaomin Yan; Xingsen Xue; Guangjian He; Jiangkai Lin; Hua Feng; Weihua Chu (Molecular Neurobiology, 2025)

Green manuring increases network complexity and deterministic assembly of diazotrophic community in a subtropical paddy soil - Xianchu Su; Luyuan Sun; Yuntao Kang; Mengmeng Feng; Junkang Zhu; Anqi Wang; Zi-Yang He; Shengsheng Jin; Jia Liu; Ji-Zheng He; Yongxin Lin (Applied Soil Ecology, 2025)

Enhancing rejection of short-chain per- and polyfluoroalkyl substances by tailoring the surface charge of nanofiltration membranes - Yue Zhi; Xiaoqing Zhao; Ao Shuai; Yonghui Jia; Xinyi Cheng; Shihong Lin; Feng Xiao; Le Han; Hongxiang Chai; Qiang He; Caihong Liu (Water Research, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Analysis of geothermal resources in the northeast margin of the Pamir plateau - Feng Chen; Jingyu Lin; Genyi He; Shuai Wang; Xuelian Huang; Boyuan Zhao; Sijia Wang; Yongjie Han; Shihua Qi (Geothermics, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Comammox Nitrospira and ammonia-oxidizing bacteria are metabolically active in a subtropical estuarine wetland - Mengmeng Feng; Yongxin Lin; Guiping Ye; Zi-Yang He; Dong Zhu; Hang-Wei Hu; Yuheng Cheng; Fengyi Han; Ping Yang; Ji-Zheng He (Applied Soil Ecology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

Using isotope-tracer method with deuterium for quantitative study of hydrogen activation mechanism in direct coal liquefaction - Xiao-Dong Zhou; Xue-Long Yin; Lang Liu; Xue-Li Huang; Jing-Mei Liu; Ting Liu; He Lin; Feng-Yun Ma (Fuel, 2025)

Directional induction of hydrogen spillover enhancing H2O resistance of Ca-Ni-based dual-function materials for integrated CO2 capture and in-situ methanation - Linjia Li; Yiran Zhang; Xiaochao Wang; Junfeng Lu; Jiaqi Feng; Shu Zhao; Wei Qiu; Zhen Huang; He Lin (Chemical Engineering Journal, 2025)

Role of MFN2 in bovine embryonic development and the mitigation of ER stress - Shu-Ming Shi; Bing Hu; Zhi-Chao Chi; Lin-Yi Qu; Li-Ying Liu; Yu-Yan He; Guan-Lin Jia; Jing-Hang Li; Ilkeun Kong; Yong-Xun Jin; Xian-Feng Yu (Animal Reproduction Science, 2025)

New insights of 4-Methylesculetin in alleviating the effect of aflatoxin B1 on flesh quality of grass carp (Ctenopharyngodon idella) - Xiang-Ning He; Jia-Jia Zhang; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; He-Qun Shi; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Description of Albidovulum litorale sp. nov., Albidovulum marisflavi sp. nov., Albidovulum salinarum sp. nov., and Albidovulum sediminicola sp. nov., and proposal for reclassification of the genus Defluviimonas as a later heterotypic synonym of Albidovulum - Wei He; Dao-Feng Zhang; Xing-Jie Li; Hong-Chuan Wang; Lin-Qiong Wang; Yang Yuan (Systematic and Applied Microbiology, 2025)

Genome-wide characterization and comparative transcriptomics unravel CpMADS47 as a positive regulator during fruit ripening and softening in Chinese cherry - Tai Tian; Shiqing Yin; Fengting Huang; Longqiang Feng; Yan Ma; Hao Wang; Jing Zhang; Wen He; Yuanxiu Lin; Yunting Zhang; Mengyao Li; Zhiwei Wu; et al. (Postharvest Biology and Technology, 2025)

Harnessing metal-metal interactions for simultaneously boosting photocatalytic hydrogen and benzaldehyde production - Yajie Feng; Chi Lin; Yifei Huang; Bing Li; Yingxin He; Jiangping Ma; Chaogang Ban; Lujie Ruan; Hongxing Jia; Xiaoping Tao; Liyong Gan; Xiaoyuan Zhou (Chemical Engineering Journal, 2025)

Synergistic effects of accompanying heterotrophic bacteria on sulfide-based autotrophic denitrification - Yu-Lin Han; Zhen-Chuan Wu; Feng Jiang; He-Ping Zhao (Chemical Engineering Journal, 2025)

Dynamic surface potential gradient for charged droplet manipulation - Jie Wang; Xuanming Hu; Haiye Feng; Yunxin Tang; Guo Sun; Shiji Lin; Lirong He; Qiangqiang Sun; Shaobing Zhou (Chemical Engineering Journal, 2025)

GWAS analysis revealed genomic loci and candidate genes associated with the 100-seed weight in high-latitude-adapted soybean germplasm - Javaid Akhter Bhat; Hui Yu; Lin Weng; Yilin Yuan; Peipei Zhang; Jiantian Leng; Jingjing He; Beifang Zhao; Moran Bu; Songquan Wu; Deyue Yu; Xianzhong Feng (Theoretical and Applied Genetics, 2025)

Two novel butyrolactone lignan dimers from leaves of Castanopsis chinensis and their anti-inflammatory activities - Ya-Feng Wang; Ping Lin; Nao Pang; Zhang-Bin Liu; Bing-Yuan Yang; Rui-Jie He; Yong-Lin Huang (Journal of Natural Medicines, 2025)

Cross-sectional and Longitudinal Associations Between Metal Mixtures and Serum C3, C4: Result from the Manganese‑exposed Workers Healthy Cohort - Sencai Lin; Junxiu He; Yinghua Zhou; Yu Bao; Xiuming Feng; Hong Cheng; Haiqing Cai; Sihan Hu; Lin Wang; Yuan Zheng; Mengdi Zhang; Qinghua Fan; et al. (Biological Trace Element Research, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

The gratitude model of body appreciation and intuitive eating: Replication and extension of the model to explain intuitive eating facets among young adult women in China - Zizhen Huang; Siyu Wang; Yitong Lin; Tianxiang Cui; Wesley R. Barnhart; Christina M. Gaggiano; Feng Ji; Jinbo He (Appetite, 2024)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

The rational design of ratiometric probe based on fluorescence carbon dots and its PVA film platform for the detection of Hg2+: Tunable mechanism and the performance - Qiuyan Hu; Haiying Lin; Qingge Feng; Xianghua Wu; Lixin Huang; Yu Duan; Wenlu Lan; Zixuan Chen; Lianghong Li; Jiatong Lv; Jie He; Chun Lv; et al. (Journal of Environmental Chemical Engineering, 2024)

The combination of HSI and NMR techniques with deep learning for identification of geographical origin and GI markers of Lycium barbarum L. - Chengcheng He; Xin Shi; Haifeng Lin; Quanquan Li; Feng Xia; Guiping Shen; Jianghua Feng (Food Chemistry, 2024)

Soy protein isolate ameliorate gel properties by regulating the non-covalent interaction between epigallocatechin-3-gallate and myofibrillar protein - Ying Li; Yijun Zhang; Gongchen He; Ziyan Qiao; Rong Yang; Xi Zhou; Lin Chen; Xianchao Feng (Food Chemistry, 2024)

Association of hypertension status and exposure to atmospheric ozone improvement with cognitive decline in China - Lin Liu; Guodong He; Zhiqiang Nie; Yingqing Feng; Yuqing Huang (Air Quality, Atmosphere & Health, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Study on susceptibility differences of Tetranychus cinnabarinus (Boisduval) males and females to acaricides - Weiwei Sun; Sihan Chen; Lei Liu; Zhixin Jiang; Kaiyang Feng; Lin He (Pesticide Biochemistry and Physiology, 2024)

Improved identification and monitoring of meteorological, agricultural, and hydrological droughts using the modified nonstationary drought indices in the Yellow River Basin of China - Ben Niu; Yi Li; De Li Liu; Lulu Xie; Lei Wang; Xiaohui Jiang; Hao Feng; Qiang Yu; Jianqiang He; Haixia Lin (Journal of Hydrology, 2024)

Observations of avalanche–substrate interactions in the Iymek rock avalanche deposit: A possible causative mechanism - Anwen Shi; Yufeng Wang; Qiangong Cheng; Qiwen Lin; Zhiyi Feng; Ke He; Fujun Niu; Zhang Song (Engineering Geology, 2024)

Robust self-healing ion-conductive interlocking dual-network binder based on gradient dynamic bonding for advanced SiO anodes in Li-Ion batteries - De He Weng; Liu Zhen Wu; Zi Feng He; Dong Yu Zhu; Yuan Li; Bole Ma; Qiyu Liu; Liheng Chen; Zhan Lin; Xueqing Qiu (Chemical Engineering Journal, 2024)

Automated counting and classifying Daphnia magna using machine vision - Yang Ma; Wenping Xiao; Jinguo Wang; Xiang Kuang; Rongqin Mo; Yanfang He; Jianfeng Feng; Hengling Wei; Liwen Zheng; Yufei Li; Peixin Liu; Hao He; et al. (Aquatic Toxicology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Malachite green and related substances in environmental samples: Updates on pretreatment and analysis methods - Zu-Yi Chen; Bing-lin He; Yu Bian; Yuan Zhang; Xue-song Feng (Journal of Environmental Chemical Engineering, 2024)

Unraveling the mechanism of selective dissolution in anthracite coal for enhanced permeability through sodium hypochlorite oxidation treatment - Yu Lu; Yili Kang; Zhigang Li; Ming Yue; Teng Zhang; Feng He; Chong Lin; Yue Hu; Ying Li; Zhenjiang You (Fuel, 2024)

Protective Effect of Protocatechuic Aldehyde on Cerebral Ischemia/Reperfusion Injury in Rats through Blood—Brain Barrier Protection - F. He; J. Feng; H. Sun; Y. Xu; H. Yan; X. Song; Y. Wang; X. Li; Q. Lin (Bulletin of Experimental Biology and Medicine, 2024)

A systematic review and meta-analysis on the root effects and toxic mechanisms of rare earth elements - Chenyi He; Yiping Feng; Yirong Deng; Longyong Lin; Sheng Cheng (Chemosphere, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Modulating ferroptosis for the prevention of urinary stone recurrence: An innovative strategy employing Tetrahedral Framework Nucleic acids and Polydatin conjugates - Shijian Feng; Ran Yan; Cai Tang; Zhaofa Yin; Bohan Liu; Pengan Chen; Yushi He; Liang Zhou; Yunfeng Lin (Chemical Engineering Journal, 2024)

Heparin mimicking sulfonated polyester synergistically promotes bacterial Infected-Wound healing with ROS responsive cinnamaldehyde based prodrugs - Haiwei Liu; Pengfei Shan; Yingwen Lu; Xiaoyue Lian; Feng He; Jinxiang Xiao; Linan Qiu; Zhenghao Liu; Zuobin Gan; Qingshan Yan; Yupeng Qiu; Wenwen Lin; et al. (Chemical Engineering Journal, 2024)

Down-regulation of RTEL1 Improves M1/M2 Macrophage Polarization by Promoting SFRP2 in Fibroblasts-derived Exosomes to Alleviate COPD - He-Ping Xu; Feng Zhan; Hong Wang; Jie Lin; Huan Niu (Cell Biochemistry and Biophysics, 2024)

Glucoconjugated monoterpene indole alkaloids with xanthine oxidase inhibitory activity from Ophiorrhiza japonica - Bao-Bao Shi; Fan Xu; Guang-Ru Zhang; Yu He; Qing Liu; Meng-Lin Feng; Zheng-Hui Li; Ji-Kai Liu (Phytochemistry, 2024)

Three new chemical constituents of Senecio raphanifolius - Shu-Wen Huang; Huan He; Zhi-Qiang Li; Yu-Wei Wang; Yuan-Ying Fang; Yu-Lin Feng; Zhi-Feng Li; Qi Wang (Phytochemistry Letters, 2024)

Constructing highly active vanadyl species for efficient selective catalytic reduction of NO - Chunxi Lin; Zhihua Lian; Weidong Huang; Qiang Wang; Hui Zhang; XiaoFeng Liu; Feng Deng; Xiaoyan Shi; Wenpo Shan; Hong He (Journal of Environmental Chemical Engineering, 2024)

Antibacterial and anti-inflammatory synergistic effects of double-layer hydrogel promoting bacterial wound healing - Chunyang Li; Jin-Tao Wang; Kuili Liu; Hongwei Ding; Qing-Feng Li; Gaofeng Liang; Lin Jin; Deyan He (Chemical Engineering Journal, 2024)

Warming enhanced the interaction effects of fungi and fungivores and soil potassium mineralization in tropical forest - Feng Sun; Guanzhao Yan; Wei Lin; Wei He; Xianli Cheng; Yingwen Li; Akash Tariq; Jordi Sardans; Josep Penuelas; Jinchuang Wang; Mei Wang; Yuelin Li; et al. (CATENA, 2024)

HAX1-Overexpression Augments Cardioprotective Efficacy of Stem Cell-Based Therapy Through Mediating Hippo-Yap Signaling - Wen-Feng Cai; Lin Jiang; Jialiang Liang; Suchandrima Dutta; Wei Huang; Xingyu He; Zhichao Wu; Christian Paul; Xiang Gao; Meifeng Xu; Onur Kanisicak; Junmeng Zheng; et al. (Stem Cell Reviews and Reports, 2024)
Although stem/progenitor cell therapy shows potential for myocardial infarction repair, enhancing the therapeutic efficacy could be achieved through additional genetic modifications. HCLS1-associated protein X-1 (HAX1) has been identified as a versatile modulator responsible for cardio-protective signaling, while its role in regulating stem cell survival and functionality remains unknown. In this study, we investigated whether HAX1 can augment the protective potential of Sca1 + cardiac stromal cells (CSCs) for myocardial injury. The overexpression of HAX1 significantly increased cell proliferation and conferred enhanced resistance to hypoxia-induced cell death in CSCs. Mechanistically, HAX1 can interact with Mst1 (a prominent conductor of Hippo signal transduction) and inhibit its kinase activity for protein phosphorylation. This inhibition led to enhanced nuclear translocation of Yes-associated protein (YAP) and activation of downstream therapeutic-related genes. Notably, HAX1 overexpression significantly increased the pro-angiogenic potential of CSCs, as demonstrated by elevated expression of vascular endothelial growth factors. Importantly, implantation of HAX1-overexpressing CSCs promoted neovascularization, protected against functional deterioration, and ameliorated cardiac fibrosis in ischemic mouse hearts. In conclusion, HAX1 emerges as a valuable and efficient inducer for enhancing the effectiveness of cardiac stem or progenitor cell therapeutics. Graphical Abstract

CD146, a therapeutic target involved in cell plasticity - Zhenzhen Wu; Yuzhe Zang; Chuyi Li; Zhiheng He; Jingyu Liu; Zhaoqi Du; Xinran Ma; Lin Jing; Hongxia Duan; Jing Feng; Xiyun Yan (Science China Life Sciences, 2024)

Repeated Ketamine Anesthesia during the Neonatal Period Impairs Hippocampal Neurogenesis and Long-Term Neurocognitive Function by Inhibiting Mfn2-Mediated Mitochondrial Fusion in Neural Stem Cells - He Huang; Ning Wang; Jia-Tao Lin; Yong-Kang Qiu; Wei-Feng Wu; Qiang Liu; Chen Chen; Hai-Bi Wang; Yan-Ping Liu; Wei Dong; Jie Wan; Hui Zheng; et al. (Molecular Neurobiology, 2024)

Fungal composition associated with host tree identity mediates nutrient addition effects on wood microbial respiration - Zhenhong Hu; Marcos Fernández‐Martínez; Qinsi He; Zhiyuan Xu; Lin Jiang; Guiyao Zhou; Ji Chen; Ming Nie; Qiang Yu; Hao Feng; Zhiqun Huang; Sean T. Michaletz (Ecology, 2024)
Fungi are key decomposers of deadwood, but the impact of anthropogenic changes in nutrients and temperature on fungal community and its consequences for wood microbial respiration are not well understood. Here, we examined how nitrogen and phosphorus additions (field experiment) and warming (laboratory experiment) together influence fungal composition and microbial respiration from decomposing wood of angiosperms and gymnosperms in a subtropical forest. Nutrient additions significantly increased wood microbial respiration via fungal composition, but effects varied with nutrient types and taxonomic groups. Specifically, phosphorus addition significantly increased wood microbial respiration (65%) through decreased acid phosphatase activity and increased abundance of fast‐decaying fungi (e.g., white rot), while nitrogen addition marginally increased it (30%). Phosphorus addition caused a greater increase in microbial respiration in gymnosperms than in angiosperms (83.3% vs. 46.9%), which was associated with an increase in Basidiomycota:Ascomycota operational taxonomic unit abundance in gymnosperms but a decrease in angiosperms. The temperature dependencies of microbial respiration were remarkably constant across nutrient levels, consistent with metabolic scaling theory hypotheses. This is because there was no significant interaction between temperature and wood phosphorus availability or fungal composition, or the interaction among the three factors. Our results highlight the key role of tree identity in regulating nutrient response of wood microbial respiration through controlling fungal composition. Given that the range of angiosperm species may expand under climate warming and forest management, our data suggest that expansion will decrease nutrient effects on forest carbon cycling in forests previously dominated by gymnosperm species.

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Elevation-associated pathways mediate aquatic biodiversity at multi-trophic levels along a plateau inland river - Mengru Wei; Tao Feng; Yuqing Lin; Shufeng He; Hanlu Yan; Ruxia Qiao; Qiuwen Chen (Water Research, 2024)

Arbuscular mycorrhizal fungi reduce soil N2O emissions by altering root traits and soil denitrifier community composition - Tangqing He; Wei Lin; Shuo Yang; Jiaqi Du; Bhoopander Giri; Cheng Feng; Frank S. Gilliam; Fuliang Zhang; Xiaoquan Zhang; Xuelin Zhang (Science of The Total Environment, 2024)

Enhancing the phytoextraction efficiency of heavy metals in acidic and alkaline soils by Sedum alfredii Hance: A study on the synergistic effect of plant growth regulator and plant growth-promoting bacteria - Zhiqin Chen; Qizhen Liu; Dan Chen; Yingjie Wu; Yasir Hamid; Qiang Lin; Shijun Zhang; Ying Feng; Zhenli He; Xianyuan Yin; Xiaoe Yang (Science of The Total Environment, 2024)

Effect of a collagen peptide–fish oil high internal phase emulsion on the printability and gelation of 3D-printed surimi gel inks - Shanshan Lu; Zhisheng Pei; Quanhong Lu; Qian Li; Yanfu He; Aiguo Feng; Zhongyuan Liu; Changfeng Xue; Jianhua Liu; Xiangdong Lin; Yongcheng Li; Chuan Li (Food Chemistry, 2024)

An improved representative of stomatal models for predicting diurnal stomatal conductance at low irradiance and vapor pressure deficit in tropical rainforest trees - Wei Xue; Xue-min He; Quan Wang; Pei-jun Shi; Guang-hui Lv; Jian-feng Huang; Da Yang; Jiao-lin Zhang (Agricultural and Forest Meteorology, 2024)

Three new quinic acid derivatives and a new shikimic acid derivative from the leaves of Castanopsis orthacantha - Xue-Xue Cheng; Ya-Feng Wang; Rui-Jie He; Bing-Yuan Yang; Zhang-Bin Liu; Yong-Lin Huang (Phytochemistry Letters, 2024)

Facile construction of a cobalt-incorporated N-doped porous carbon from biomass for highly efficient removal of tetracycline - Fengzhen Wu; Jiamei Qian; Changfu He; Yiming Mao; Guanfeng Lin; Feng Zhu; Yandan Chen; Jianhua Lv; Biao Huang; Beili Lu (Journal of Environmental Chemical Engineering, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

Gold nanocluster-based ratiometric fluorescence immunoassay for broad-spectrum screening of five eugenols - Lin Luo; Zhen-Xi He; Bao-Zhu Jia; Rui-Yao Kang; Wen-Feng Zhang; Ri-Ming Huang; Zhen-Lin Xu (Analytica Chimica Acta, 2024)

The composition and differences of antimony isotopic in sediments affected by the world's largest antimony deposit zone - Huiji Liu; Guangyi Sun; Mengchang He; Xinbin Feng; Chunye Lin; Wei Ouyang; Xitao Liu (Water Research, 2024)

Comparative study on the nutrient recovery from source-separated urine using magnesium-air fuel cell in different operating modes - Lin-Feng He; Shu-Jie Hu; Di Wu; Meng-Yue Zhang; Hong Liu; Yuan Liu (Process Safety and Environmental Protection, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Distinctive shear zones demonstrate pervasive laminar cataclastic flow throughout the gigantic Iymek rock avalanche - Anwen Shi; Yufeng Wang; Qiangong Cheng; Qiwen Lin; Tianhua Li; Zhiyi Feng; Ke He; Fujun Niu; Zhang Song (Geomorphology, 2024)

Triterpene hexahydroxydiphenoyl ester and phenol glucosides from the leaves of Castanopsis eyrie (Champ. ex Benth.) Hutch - Bing-Yuan Yang; Nao Pang; Rui-Jie He; Ya-Feng Wang; Yong-Lin Huang (Natural Product Research, 2024)

Higher stochasticity in comammox Nitrospira community assembly in upland soils than the adjacent paddy soils at a regional scale - Mengmeng Feng; Yongxin Lin; Zi-Yang He; Hang-Wei Hu; Shengsheng Jin; Jia Liu; Song Wan; Yuheng Cheng; Ji-Zheng He (Science of The Total Environment, 2024)

Microplastics and cadmium affect invasion success by altering complementarity and selection effects in native community - Feng He; Jianfan Sun; Justin S.H. Wan; Mohsin Nawaz; Qaiser Javed; Linxuan Pan; Wajid Ali Khattak; Yanwen Bo; Yan Xiang; Guangqian Ren; Xin Lin; Daolin Du (Science of The Total Environment, 2024)

Application of data-driven mixing parameterization scheme in a regional ocean model - Qingfeng Feng; Guoqing Han; Yu Liu; Xiayan Lin; Bo Li; Xiaoqian Gao; Changming Dong; Yinghui He; Haili Wang (Ocean Modelling, 2024)

Co-foliar application of zinc and nano-silicon to rice helps in reducing cadmium exposure risk: Investigations through in-vitro digestion with human cell line bioavailability assay - Qiang Lin; Yasir Hamid; Honhang Wang; Min Lu; Xuerui Cao; Tong Zou; Zhiqin Chen; Bilal Hussain; Ying Feng; Tingqiang Li; Zhenli He; Xiaoe Yang (Journal of Hazardous Materials, 2024)

Mechanistic insights into the adsorption and extraction of rare earth ions using oxygen- and phosphorus-doped porous graphitic carbon nitride - Yiping Feng; Pingping Chen; Xingye Lian; Chenyi He; Chaoyu Zheng; Haijian Lu; Longyong Lin; Guoguang Liu; Yirong Deng (Journal of Environmental Chemical Engineering, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

New perspectives on the mechanism of curcumin in the gill mucosal immune barrier damaged by ochratoxin A in juvenile grass carp (Ctenopharyngodon idella) - Piao Zhao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; He-Qun Shi; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2024)

Intra-annual stem radial growth of Qinghai spruce and its environmental drivers in the Qilian Mountains, northwestern China - Quanyan Tian; Zhibin He; Shengchun Xiao; Xiaomei Peng; Pengfei Lin; Xi Zhu; Xiangyan Feng (Science of The Total Environment, 2024)

Biocontrol activity of an endophytic Alternaria alternata Aa-Lcht against apple Valsa canker - Yanting He; Runze Tian; Chengyu Gao; Lin Ji; Xiao Liu; Hao Feng; Lili Huang (Pesticide Biochemistry and Physiology, 2024)

Different crystalline manganese dioxide and biochar co-conditioning aerobic composting: Reduced ammonia volatilization and improved organic fertilizer quality - Weijiang He; Shaopeng Rong; Jixiang Wang; Yingjie Zhao; Yunyi Liang; Junxia Huang; Lin Meng; Yanfang Feng; Lihong Xue (Journal of Hazardous Materials, 2024)

A quantitative model to estimate major oxide abundances on the Moon based on in situ reflectance spectral data of Chang'e missions - Zhenxing Zhao; Yazhou Yang; Xing Wu; Yang Liu; Feng Zhang; Rui Xu; Zhiping He; Yangting Lin; Yongliao Zou (Icarus, 2024)

Revealing the correlation between the performance of silica-based DAC adsorbents and their pore natures - Yiran Zhang; Shu Zhao; Linjia Li; Jiaqi Feng; Wei Qiu; Zhidong Wei; Xinling Li; Zhen Huang; He Lin (Gas Science and Engineering, 2024)

Theoretical model of circular concrete-filled aluminum alloy tubular short columns under axial compression - Xi-Feng Yan; Meng-Nan He; Ji-Ping Hao; Siqi Lin (Engineering Structures, 2024)

Impact of urban land development on carbon emission performance based on a multidimensional framework - Xinhui Feng; Xinle Lin; Yan Li; Jiayu Yang; Er Yu; Congying He; Kaige Lei; Weiming Gao (Environmental Impact Assessment Review, 2024)

In situ Fe isotope analysis of Cr-rich iron oxides using pure chromium metal for isobaric interference corrections by femtosecond LA–MC–ICP–MS - Xinting Lü; Detao He; Yongsheng Liu; Ming Li; Jie Lin; Wei Chen; Lüyun Zhu; Ao Yang; Yantong Feng; Zhenyi Liu; Xianli Zeng; Zhaochu Hu (Chemical Geology, 2024)

A global synthesis of the patterns of genetic diversity in endangered and invasive plants - Zhi-Zhou He; Gisela C. Stotz; Xiang Liu; Jia-Jia Liu; Yu-Guo Wang; Ji Yang; Lin-Feng Li; Wen-Ju Zhang; Peng Nan; Zhi-Ping Song (Biological Conservation, 2024)

The Alasu rock avalanche in the Tianshan Mountains, China: fragmentation, landforms, and kinematics - Qi-wen Lin; Yu-feng Wang; Qian-gong Cheng; Jing Huang; Hao-ran Tian; Guo-xiang Liu; Ke He (Landslides, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Evaluation of the dietary L-valine on fish growth and intestinal health after infection with Aeromonas veronii - Quanquan Cao; Ju Zhao; Lingjie He; Tianran Zhang; Lin Feng; Weidan Jiang; Pei Wu; Juan Zhao; Haifeng Liu; Jun Jiang (Aquaculture, 2024)

A particle-scale insight into the face stability of shallow EPB shield tunnels in dry cobble-rich soil - Jun Wang; Guojin Lin; Rui Tang; Yan Zhang; Zhigang Yao; Kun Feng; Ning Tian; Ziquan Chen; Chuan He (Tunnelling and Underground Space Technology, 2024)

Foliar application of plant growth regulators for enhancing heavy metal phytoextraction efficiency by Sedum alfredii Hance in contaminated soils: Lab to field experiments - Zhiqin Chen; Qizhen Liu; Shijun Zhang; Yasir Hamid; Jiapan Lian; Xiwei Huang; Tong Zou; Qiang Lin; Ying Feng; Zhenli He; Xiaoe Yang (Science of The Total Environment, 2024)

Absolute age and temperature of belemnite rostra: Constraints on the Early Cretaceous cooling event - Tianyang Wang; Peng Yang; Songlin He; René Hoffmann; Qinghai Zhang; Alex Farnsworth; Yue-xing Feng; Hasina Nirina Randrianaly; Jing Xie; Yahui Yue; Jian-xin Zhao; Lin Ding (Global and Planetary Change, 2024)

Inhibition mechanisms of biochar-derived dissolved organic matter to triclosan photodegradation: A remarkable role of aliphatics - Lin Wang; Jing Feng; Quan Chen; Hao Jiang; Jing Zhao; Zhaofeng Chang; Xinhua He; Fangfang Li; Bo Pan (Environmental Pollution, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

Age, growth, reproduction and status of resource development of Ptychidio jordani , a critically endangered freshwater fish in the Hongshui River, China - Jiayang He; Zhiqiang Wu; Liangliang Huang; Yangyan Sun; Dongjie Wang; Yong Lin; Anyou He; Jie Feng; Hao Liu (Journal of Fish Biology, 2024)
The age, growth, reproduction and resource development status of Ptychidio jordani , as a critically endangered freshwater fish in the Hongshui River, China, was studied in this work. A total of 525 specimens were collected monthly using the cages and gillnets from October 2021 to September 2022 in the Hongshui River. The scale was used for age determination, and the maximum age for both female and male was estimated to be 5 years and 3 years, respectively. Female and male P. jordani showed different growth patterns, which were expressed as L t = 261.3 (1‐e −0.4885( t −0.1476) ) and L t = 251.2 (1‐e −0.4758( t +0.9643) ), respectively. The overall sex ratio was 1:0.47 (female:male). Female attained sex maturity at 2.34 years (192 mm body length). Month variation of the gonad somatic index indicated that the spawning period occurred from April to October. The absolute fecundity was estimated at 9046 ± 3434 eggs per individual, and the relative fecundity was 38.08 ± 15.77 eggs per gram. The exploitation rate of female and male was 0.233 and 0.495, which indicated that P. jordani was not overfishing. This study provided data on the key life‐history traits of P. jordani , which has not been known previously and is essential for conservation strategy and policy development.

Integrating fecal pollution markers and fluorescence analysis for water quality assessment of urban river - Zejun Liu; Jinlong Yuan; Yingying Lin; Feng Lin; Bingjun Liu; Qidong Yin; Kai He; Xinfeng Zhao; Haoxian Lu (Science of The Total Environment, 2024)

Vegetation-cover control of between-site soil temperature evolution in a sandy desertland - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Yalu Han; Shuang Feng; Lin Miao; Chen Liu (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Pressure–temperature–time path of ultrahigh-pressure metamorphic terranes constrained by zircon petrochronology: A case study of orthogneisses from the northern Sulu belt, China - Peng Feng; Hao Deng; Yang Zhang; Qing-Lin Sui; Hai-Yang He; Yan-Shi Xie; Liang Chen; Xian-Zhe Duan; Wen-Zhou Xiao; Xia-Wen Li; Nan Li (Journal of Asian Earth Sciences, 2024)

Activate the filtration capability of 3.5 nm ultra-large pores and eliminate the requirement of pore homogeneity for carbon nanotube array membranes - Na Li; Zemeng Feng; Yiyue He; Zhaogang Peng; Xiangrui Meng; Huijuan Lin; Kui Xu (Desalination, 2024)

Identification and fine-mapping of QYrAS286-2BL conferring adult-plant resistance to stripe rust in cultivated emmer wheat - Yuqin Li; Yanling Hu; Yun Jiang; Qiang Zhou; Yu He; Jingshu He; Xuejiao Chen; Xue Chen; Bo Jiang; Ming Hao; Shunzong Ning; Zhongwei Yuan; et al. (Theoretical and Applied Genetics, 2024)

Elucidating the toxicity mechanisms of organophosphate esters by adverse outcome pathway network - Wanyu He; Jiaqi Ding; Ning Gao; Lingyan Zhu; Lin Zhu; Jianfeng Feng (Archives of Toxicology, 2024)

Stress drop variations of the 2019 ML 6.0 Changning earthquake and its aftershock sequence in the southern Sichuan Basin, China - Lin Shen; Lian-Feng Zhao; Xiao-Bi Xie; Xi He; Wei-Min Wang; Zhen-Xing Yao (Tectonophysics, 2023)

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

Formation and detection of biocoronas in the food industry and their fate in the human body - Qian Wu; Mengyao Niu; Chen Zhou; Yaxiong Wang; Jianhua Xu; Lin Shi; He Xiong; Nianjie Feng (Food Research International, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Two truxinate derivatives and a phenyldilactone from the leaves of Castanopsis eyrei - Ya-feng Wang; Nao Pang; Zhen-hua Liang; Yong-lin Huang; Rui-jie He; Bing-yuan Yang; Zhang-bin Liu (Natural Product Research, 2023)

Bibliometric analysis of publications on biodegradation of plastics: Explosively emerging research over 70 years - Shan-Shan Yang; Wei-Min Wu; Ji-Wei Pang; Lei He; Meng-Qi Ding; Mei-Xi Li; Yi-Lin Zhao; Han-Jun Sun; De-Feng Xing; Nan-Qi Ren; Jun Yang; Craig S. Criddle; et al. (Journal of Cleaner Production, 2023)

Inhibitory mechanism of carboxymethyl chitosan-lotus seedpod oligomeric procyanidin nanoparticles on dietary advanced glycation end products released from glycated casein during digestion - Qian Wu; Fen Zhang; Yaxiong Wang; Jia Yan; Chen Zhou; Yang Xu; Jianhua Xu; Lin Shi; He Xiong; Nianjie Feng (Food Research International, 2023)

The metabolism of membrane lipid participates in the occurrence of chilling injury in cold-stored banana fruit - Qian Li; Han Lin; He-tong Lin; Meng-shi Lin; Hui Wang; Wei Wei; Jian-ye Chen; Wang-jin Lu; Xing-feng Shao; Zhong-qi Fan (Food Research International, 2023)

GC/QQQ coupling with metabolomics for selection of predicator of tea fermentation - Yingqing Ye; Jiazheng Lin; Junfeng Yin; Hua-Feng He (Food Research International, 2023)

Immune-microenvironment modulatory polyurethane-hyaluronic acid hybrid hydrogel scaffolds for diabetic wound treatment - Yuan Feng; Kecen Xiao; Jinlin Chen; Jingjing Lin; Yuanyuan He; Xueling He; Fuyi Cheng; Zhen Li; Jiehua Li; Feng Luo; Hong Tan; Qiang Fu (Carbohydrate Polymers, 2023)

Application of enzymatically treated Artemisia annua L. on adult grass carp (Ctenopharyngodon idella): Improved growth performance, intestinal antioxidant capacity and apical junctional complex - Qin-Qin Dai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; He-Qun Shi; Lu Zhang; Hai-Feng Mi; Jia-Yong Tang; Rui-Nan Zhang; Lin Feng (Aquaculture, 2023)

Host-derived peptide signals regulate Pseudomonas aeruginosa virulence stress via the ParRS and CprRS two-component systems - Ning-Lin Zhao; Zi-Qi Zhu; Han-Zhong Feng; Ying-Jie Song; Qin Huang; Xing-Yu Mou; Cheng Nong; Yong-Xing He; Rui Bao (Journal of Hazardous Materials, 2023)

Multi-technological integration in a smelting site: Visualizing pollution characteristics and migration pattern - Lu Tang; Wenwan Chen; Xinghua Luo; Gubin Zhang; Xiang Feng; Lin Guo; Wenyan Gao; Jin He; Guizhang Zhao; Jun Jiang; Shengguo Xue (Journal of Hazardous Materials, 2023)

Evolution of aniline degradation and nitrogen removal performance in electro-enhanced sequence batch reactor under salinity stress: Sludge characteristics and microbial diversity - Bing Lin; Bin Tan; Qian Zhang; Meng Li; Jiapeng Feng; Junhao Su; Jing He; Yunjie Zhang; Xiangyu Liu; Nanping Wu; Jiajing Chen (Environmental Pollution, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Multi-dimensional micro-nano scale manganese oxide catalysts induced chemical-based advanced oxidation processes (AOPs) in environmental applications: A critical review - Lin Lin; Junsen Wang; Zhifang Zhao; Jiayi Zhu; Aikeyidanmu Zhamaerding; Lingyun Feng; Dan Yang; Lite Meng; Chuanshu He; Wenbing Wang; Yunhui Zhang; Wei Jin (Chemical Engineering Journal, 2023)

Effects of submergence stress on germination and seedling growth of direct-seeded rice and evaluation of submergence tolerance - Rongping Zhang; Ningning Zhou; Lin Zhou; Rigui Ashi; Tingyu Feng; Keyuan Zhang; Xuehuan Liao; Lise Aer; Xia Wu; Kangning Yu; Jianchao Shu; Xuewu He; et al. (Paddy and Water Environment, 2023)

Associations of metal mixtures with thyroid function and potential interactions with iodine status: results from a cross-sectional study in MEWHC - Xiaoting Ge; Junxiu He; Sencai Lin; Yu Bao; Yuan Zheng; Hong Cheng; Haiqing Cai; Xiuming Feng; Wenjun Yang; Sihan Hu; Lin Wang; Qijing Liao; et al. (Environmental Science and Pollution Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

CDN1163, a SERCA activator, causes intracellular Ca2+ leak, mitochondrial hyperpolarization and cell cycle arrest in mouse neuronal N2A cells - Yi-Ping Huang; Wen-Wei Huang; Kun-Feng Tsai; Lian-Ru Shiao; Zih-He Yang; Shao-Yun Tseng; Yu-Hsien Lin; Cing-Yu Chen; Paul Chan; Yuk-Man Leung (NeuroToxicology, 2023)

Spatial variation in the community structure and response of benthic macroinvertebrates to multiple environmental factors in mountain rivers - Zaoli Yang; Shufeng He; Tao Feng; Yuqing Lin; Mo Chen; Qinyuan Li; Qiuwen Chen (Journal of Environmental Management, 2023)

Identification of suitable tributaries to compensate fish habitat loss in dammed rivers using environmental DNA metabarcoding - Yuqing Lin; Tao Feng; Lei Tang; Hui Zhang; Jianyun Zhang; Qiuwen Chen; Shufeng He; Ting Li (Hydrobiologia, 2023)

Anti-inflammatory ent-cleistanthane-type diterpenoids from Phyllanthus rheophyticus - Hong-Ying Yang; Pei-Zhi Huang; Qian Ma; Yue Sun; Wei-Jiao Feng; Yi-Lin He; Jian-Jun Chen; Kun Gao (Phytochemistry, 2023)

Two new isoflavones from the barks of Dalbergia hancei Benth - Xiao-Mei Li; Nao Pang; Ya-Feng Wang; Rui-Jie He; Li Ge; Bing-Yuan Yang; Ke-Di Yang; Yong-Lin Huang (Natural Product Research, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Kinetics and mechanism study of dyes degradation in electric field-promoting catalytic wet air oxidation process - Lin-Feng Zhai; Yi Hu; Shu-Ya Xu; He-You Guo; Min Sun; Jun Yu; Yan Wang (Journal of Environmental Management, 2023)

Suppression mechanism of L-lysine on the Epigallocatechin-3-gallate-induced loss of myofibrillar protein gelling potential - Mengyuan Wang; Jingchao Kang; Lin Chen; Gongchen He; Yaping Liu; Xiaojing Fan; Xin Lv; Xinglian Xu; Guanghong Zhou; Xianchao Feng (Food Research International, 2023)

Flood-driven jet flow and sedimentary regime in a river-dominated estuary - Jing Liu; Yitong Lin; Zixiao He; Feng Liu; Liangwen Jia; Wen Wei (Frontiers in Marine Science, 2023)
Sediment dynamics under floods are critical for estuarine morphological evolution. A two-dimensional coupled hydrodynamic/sediment transport numerical modeling was adapted to investigate the flood-driven jet structure and the resultant sedimentary regime in a river-dominated estuary, Modaomen Estuary, Pearl River Delta, China. The results show that the flow velocity of flood jet exhibits a Gaussian distribution in the transverse direction and shows a linear decreasing trend in the longitudinal direction. Moreover, a distinct zonation, including a zone of flow establishment (ZOFE) and a zone of established flow (ZOEF), was detected. The ZOFE was the core area of high turbidity and strong erosion and provided sufficient sediments to the ZOEF, where sediment diffused and settled. Due to the settling lag, the sediment diffusion and deposition areas were larger than those of the jet. Estuarine geomorphology regulates the shape of flood jet, which shows an asymmetry configuration with the main body located at the west side of the bifurcated estuary. Tidal dynamics play a crucial role in altering the range of jet diffusion, especially in the longitudinal direction. Increased flood intensity has little effect on the jet structure and erosion/deposition pattern, but significantly increases the magnitude of seaward current velocities and bed level changes, as well as the transverse diffusion range of jet and sedimentation.

Aflatoxin B1 exposure induced developmental toxicity and inhibited muscle development in zebrafish embryos and larvae - Xiang-Ning He; Pei Wu; Wei-Dan Jiang; Yang Liu; Sheng-Yao Kuang; Ling Tang; Hong-Mei Ren; Hua Li; Lin Feng; Xiao-Qiu Zhou (Science of The Total Environment, 2023)

Soil properties drive the bacterial community to cadmium contamination in the rhizosphere of two contrasting wheat (Triticum aestivum L.) genotypes - Min Lu; Lukuan Huang; Qiong Wang; Xuerui Cao; Qiang Lin; Zhenli He; Ying Feng; Xiaoe Yang (Journal of Environmental Sciences, 2023)

The occurrence characteristics and underlying removal mechanism of combined copper and sulfamethoxazole pollution in constructed wetlands - Lin Ma; Lingli Yang; Yi Zhang; Qiaohong Zhou; Zhenbin Wu; Feng He (Chemical Engineering Journal, 2023)

Development and application of an in-situ shipboard device for the measurement of gamma-ray emitters in seawater - Jianhua He; Christos Tsabaris; Wen Yu; Feng Lin (Journal of Environmental Radioactivity, 2023)

Evolution characteristic of atmospheric black carbon particles at a coastal site in the Pearl River Delta, China - Jing Wei; Xiao-Feng Huang; Yan Peng; Xiao-Yu Lin; Zhen-Hua Lei; Li-Ming Cao; Wen-Fei Zhu; Song Guo; Ling-Yan He (Environmental Pollution, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Cadmium mobility and health risk assessment in the soil-rice-human system using in vitro biaccessibility and in vivo bioavailability assay: Two year field experiment - Qiang Lin; Yasir Hamid; Haijun Yang; Jianfeng Jiang; Anqi Shan; Mei Wang; Bilal Hussain; Ying Feng; Tingqiang Li; Zhenli He; Xiaoe Yang (Science of The Total Environment, 2023)

Aflatoxin B1 damaged structural barrier through Keap1a/Nrf2/ MLCK signaling pathways and immune barrier through NF-κB/ TOR signaling pathways in gill of grass carp (Ctenopharyngodon idella) - Xiang-Ning He; Zhen-Zhen Zeng; Lin Feng; Pei Wu; Wei-Dan Jiang; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Aquatic Toxicology, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Effect of feeding level on growth, digestive and metabolic enzymes and antioxidant capacity in juvenile Yangtze sturgeon (Acipenser dabryanus) - Bin He; Bo Zhou; Hang Xie; Zeng-Tan Hu; Bin Wang; Jun-Lin Zhang; Qing-Zhi Li; Feng-Qi Zhao; Xing Liu; Qian-Dong Li; Tao Yan (Aquaculture, 2023)

Insights into the promotion of urine-diverting toilets based on the fertilizer efficiency of artificial phosphate ore recovered from source-separated urine - Yuan Liu; Qi Zhang; Lin-Feng He; Yang Ran; Ying-Ying Deng; Hong Liu (Resources, Conservation and Recycling, 2023)

Environmentally-friendly biorecovery of manganese from electrolytic manganese residue using a novel Penicillium oxalicum strain Z6-5-1: Kinetics and mechanism - Shuai Zhao; Bo-Wen Zheng; Yu-Cang Wang; Fei He; Li-Juan Wang; Xiong Lin; Xue-Mei Luo; Jia-Xun Feng (Journal of Hazardous Materials, 2023)

A hybrid deep learning model for regional O3 and NO2 concentrations prediction based on spatiotemporal dependencies in air quality monitoring network - Cui-lin Wu; Hong-di He; Rui-feng Song; Xing-hang Zhu; Zhong-ren Peng; Qing-yan Fu; Jun Pan (Environmental Pollution, 2023)

Unveiling the interaction mechanism between facet-dependent pyrite nanoparticles and Cr(VI) under anaerobic environment: adsorption, redox, and phase transformation - Chenrui Liu; Yun Liu; Wentao Shen; Shuangyi Lin; Hao He; Fan Li; Feng Li; Jiang Tian (Chemical Engineering Journal, 2023)

Identification and Characterization of Bacillus subtilis B9: A Diazotrophic Plant Growth-Promoting Endophytic Bacterium Isolated from Sugarcane Root - Yi-ning Di; Ling Kui; Pratiksha Singh; Lu-feng Liu; Lin-yan Xie; Li-lian He; Fu-sheng Li (Journal of Plant Growth Regulation, 2023)
Plant endophytic microorganisms, which can enhance plant growth and resistance to biotic and abiotic stresses, are untapped resources with large potential applications for crop production. However, the endophytic community is influenced by multiple factors, such as host genetics, the environment, and other microbes. Thus, it is important to characterize well-adapted endophytes from native crops. We isolated 43 endophytic bacteria from sugarcane cultivar Yunzhe-99-91. All these 43 isolates were examined in vitro for nitrogenase activity and the ability to dissolve phosphorus and produce siderophore. One of these strains, B9, identified as Bacillus subtilis and showed maximum plant growth promotion, was selected for detailed studies. B9 promoted the production of organic acids such as propionic acid, acetic acid, malic acid and citric acid, and the production of phytohormones, including indole-3-acetic acid, cytokinin, 6-benzyladenine, and zeatin. Moreover, B9 significantly promoted the growth of sugarcane plantlets and increased the content of nitrogen, phosphorus, and potassium in the seedlings by 29.26%, 50.78%, and 15.49%, respectively. The photosynthetic rate, root development, and chlorophyll content were also improved with varying degrees compared to the non-inoculated control. The cotyledon and hypocotyl of sugarcane gems germinated faster when co-cultured with the B9 strain compared with control group. Colonization assay showed that B9 was mainly colonized in the roots, followed by the stems and leaves. In conclusion, the positive interaction between endophytic strain B9 and sugarcane may provide long-lasting benefits and a direction for developing and utilizing B9 as a biofertilizer for sugarcane cultivation to decrease fertilizer application.

Occurrence, bioaccumulation and trophic transfer of organophosphate esters in marine food webs: Evidence from three bays in Bohai Sea, China - Wanyu He; Jiaqi Ding; Wanni Liu; Wenjue Zhong; Lingyan Zhu; Lin Zhu; Jianfeng Feng (Science of The Total Environment, 2023)

Acute exposure to microcystins affects hypothalamic-pituitary axes of male rats - Ting Shi; Lin-Lin Xu; Liang Chen; Jun He; Ye-Ke Wang; Feng Chen; Yang Chen; John P. Giesy; Yu-Ting Wang; Qian-Hui Wu; Wen-Li Xu; Jun Chen; et al. (Environmental Pollution, 2023)

Injectable Host-Guest supramolecular hydrogel Co-Delivers hydrophobic and hydrophilic agents for enhanced wound healing - Jie Xu; Kangning Wang; Yanyan Li; Yue Li; Bingxin Li; Hangqi Luo; Huiling Shi; Xueran Guan; Ting Zhang; Yixiao Sun; Feng Chen; Huacheng He; et al. (Chemical Engineering Journal, 2023)

Dexmedetomidine alleviates acute lung injury by promoting Tregs differentiation via activation of AMPK/SIRT1 pathway - Zheng-tao Zhang; Ke Xie; Ren-jie Luo; Dan-ying Zhang; Zhi-wei He; Ke-feng Li; Shi-hui Lin; Fang Xu (Inflammopharmacology, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Rainfall interception measurements and modeling in a semiarid evergreen spruce (Picea crassifolia) forest - Junjun Yang; Zhibin He; Jianmin Feng; Pengfei Lin; Jun Du; Lingxia Guo; Yufeng Liu; Jialiang Yan (Agricultural and Forest Meteorology, 2023)

Effects of Spartina alterniflora Invasion and Mangrove Restoration on Soil Microbial Functional Diversity - Yongni He; Genmei Lin; Xinyi Gao; Yiting Cao; Naxu Hu; Rui Li; Jianxiang Feng (Journal of Soil Science and Plant Nutrition, 2022)

Correction to: MiR‑30c‑1‑3p targets matrix metalloproteinase 9 involved in the rupture of abdominal aortic aneurysms - Lin Yang; Hong‑Gang Sui; Meng‑Meng Wang; Jia‑Yin Li; Xiao‑Feng He; Jing‑Yuan Li; Xiao‑Zeng Wang (Journal of Molecular Medicine, 2022)

Trace Element Changes in the Plasma of Autism Spectrum Disorder Children and the Positive Correlation Between Chromium and Vanadium - Jun Zhang; Jing Lin; Xiying Zhao; Fang Yao; Chengyun Feng; Zhijun He; Xueshan Cao; Yan Gao; Naseer Ullah Khan; Margy Chen; Peng Luo; Liming Shen (Biological Trace Element Research, 2022)

Three new compounds from the leaves of Castanopsis tibetana Hance - Ya-Feng Wang; Rui-Jie He; Dian-Peng Li; Yong-Lin Huang (Natural Product Research, 2022)

HC-1119, a deuterated Enzalutamide, inhibits Migration, Invasion and Metastasis of the AR-positive triple-negative breast Cancer cells - Xuehong Wu; Wanru Feng; Mao Yang; Xunxi Liu; Mengdi Gao; Xinghai Li; Lin Gan; Tao He (Molecular Biology Reports, 2022)
Triple-negative breast cancers (TNBCs) are aggressive, and they develop metastasis at earlier stages, relapse more frequently, and exhibits poorer prognosis than other subtypes of breast cancer. Due to the lack of estrogen receptor for endocrine therapy and HER2 for targeted therapy, new targeted therapies for TNBCs are urgently needed. Enzalutamide is a second-generation androgen receptor (AR) inhibitor, and HC-1119 is a new synthetic deuterated enzalutamide. Owing to the isotope effect, HC-1119 has many advantages over enzalutamide, including slow metabolism, high plasma concentration and low brain exposure. However, the efficacy of HC-1119 in inhibition of AR function in triple-negative breast cancer (TNBC) has not been studied. In this study, we found high-level AR expression in both Hs578T and SUM159PT TNBC cell lines. Activation of AR by dihydrotestosterone (DHT) in both cell lines increased AR protein, induced AR-nuclear localization, enhanced cell migration and invasion in culture, and promoted liver metastasis in mice. Importantly, cotreatment with HC-1119 of these cells efficiently abolished all of these effects of DHT on both Hs578T and SUM159PT cells. These results indicate that HC-1119 is a very effective new second-generation AR antagonist that can inhibit the migration, invasion and metastasis of the AR-positive TNBC cells.

Temperature has a strong impact on the abundance and community structure of comammox Nitrospira in an Ultisol - Mengmeng Feng; Zi-Yang He; Jianbo Fan; An-Hui Ge; Shengsheng Jin; Yongxin Lin; Ji-Zheng He (Journal of Soils and Sediments, 2022)

Construction of a core germplasm bank of upland cotton (Gossypium hirsutum L.) based on phenotype, genotype and favorable alleles - Peng Han; Xiaomin Tian; Ying Wang; Cong Huang; Yizan Ma; Xiaofeng Zhou; Yu Yu; Dawei Zhang; Haijiang Xu; Yang Cao; Bo Zhu; Zhenxiu Feng; et al. (Genetic Resources and Crop Evolution, 2022)

Dynamic response and failure evolution of low-angled interbedding soft and hard stratum rock slope under earthquake - Jun Feng; Yingbin Zhang; Jianxian He; Hui Zhu; Lin Huang; Wentao Mao; Haiying Fu; Dejian Li (Bulletin of Engineering Geology and the Environment, 2022)

An integrated analysis of pond ecosystem around Poyang Lake: assessment of water quality, sediment geochemistry, phytoplankton and benthic macroinvertebrates diversity and habitat condition - Wei Liu; Qiyang Tan; Yifan Chu; Jinmei Chen; Lingli Yang; Lin Ma; Yi Zhang; Zhenbin Wu; Feng He (Aquatic Ecology, 2022)

Engineering an oilseed crop for hyper-accumulation of carotenoids in the seeds without using a traditional marker gene - Ming-Xia He; Jie-Lin Wang; Yuan-Yuan Lin; Jun-Chao Huang; Ai-Zhong Liu; Feng Chen (Plant Cell Reports, 2022)

MiR-30c-1-3p targets matrix metalloproteinase 9 involved in the rupture of abdominal aortic aneurysms - Lin Yang; Hong-Gang Sui; Meng-Meng Wang; Jia-Yin Li; Xiao-Feng He; Jing-Yuan Li; Xiao-Zeng Wang (Journal of Molecular Medicine, 2022)
Abdominal aortic aneurysm (AAA) can be fatal if ruptured, but there is no predictive biomarker. Our aim was to evaluate the prognostic potential of microRNAs (miRNAs/miRs) in an AAA mouse model and patients with unruptured AAA (URAAA) and ruptured AAA (RAAA). Among the 64 miRNAs differentially expressed in mice with AAA compared to control, miR-30c-1-3p, miR-432-3p, miR-3154, and miR-379-5p had high homology with human miRNAs. MiR-30c-1-3p plasma levels were significantly lower in patients with RAAA than in those with URAAA or control and tended to negatively correlate with the maximum aortic diameter ( r = −0.3153, P = 0.06109). MiR-30c-1-3p targeted matrix metalloproteinase ( MMP)-9 mRNA through the coding region and downregulated its expression in vitro. MMP-9 plasma concentrations were significantly higher in the RAAA group than in the URAAA group ( P < 0.001) and were negatively associated with miR-30c-1-3p levels ( r = −0.3671, P = 0.01981) and positively–with the maximal aortic diameter ( r = 0.6251, P < 0.0001). The optimal cutoff values for MMP-9 expression and the maximal aortic diameter were 461.08 ng/ml and 55.95 mm, with areas under the curve of 0.816 and 0.844, respectively. Our results indicate that plasma levels of miR-30c-1-3p and MMP-9 may be candidate biomarkers of AAA progression. Key messages Downregulation of miR-30c-1-3p expression and upregulation of its potential target MMP-9 are predictors of the devastation of AAA. Downregulation of miR-30c-1-3p expression and its downstream impact on MMP-9 have a potential on predicting the development and rupture of AAA.

Temporal Dynamics in Energy Fluxes and Trophic Structure of a Portunus trituberculatus Polyculture Ecosystem During Different Culture Periods - Jie Feng; Xiang-Li Tian; Shuang-Lin Dong; Rui-Peng He; Kai Zhang; Dong-Xu Zhang; Qing-Qi Zhang (Frontiers in Marine Science, 2022)
Swimming crab ( Portunus trituberculatus ) are an important aquaculture species in eastern coastal areas of China. To improve the understanding of P. trituberculatus culture ecosystem functioning, the dynamics of energy flow and trophic structure of a P. trituberculatus polyculture system (co-culture with white shrimp Litopenaeus vannamei and short-necked clam Ruditapes philippinarum ) were investigated in this study. Three Ecopath models representing the early, middle, and late culture periods of a P. trituberculatus polyculture ecosystem, respectively, were constructed to compare ecosystem traits at different culture periods. The results demonstrated that detritus was the main energy source in this polyculture ecosystem, and most of the total system throughput occurred at trophic levels I and II. Artificial food input and consumption by the culture organisms increased from early to middle and late periods, which produced marked impacts on biomass structure and primary production. R. philippinarum was considered to have a dominant influence on phytoplankton community dynamics which changed from nano- to pico-phytoplankton predominance, from the middle to the late period. Considering the low utilization efficiency of pico-phytoplankton production, large amounts of detritus accumulated in the sediment in the late period, which may constitute a potential risk for the ecosystem. Ecological network analyses indicated that the total energy flow and level of system organization increased from the early to the middle and late periods, whereas food web complexity and system resilience decreased from early to middle and late periods, which may indicate a trend of decreasing ecosystem stability. The system may be further optimized by increased stocking density of R. philippinarum and by introducing macro-algae at a suitable biomass to increase ecosystem stability, energy utilization efficiency, and aquaculture production.

Metabolic tuning of a stable microbial community in the surface oligotrophic Indian Ocean revealed by integrated meta-omics - Zhang-Xian Xie; Ke-Qiang Yan; Ling-Fen Kong; Ying-Bao Gai; Tao Jin; Yan-Bin He; Ya-Yu Wang; Feng Chen; Lin Lin; Zhi-Long Lin; Hong-Kai Xu; Zong-Ze Shao; et al. (Marine Life Science & Technology, 2022)
Understanding the mechanisms, structuring microbial communities in oligotrophic ocean surface waters remains a major ecological endeavor. Functional redundancy and metabolic tuning are two mechanisms that have been proposed to shape microbial response to environmental forcing. However, little is known about their roles in the oligotrophic surface ocean due to less integrative characterization of community taxonomy and function. Here, we applied an integrated meta-omics-based approach, from genes to proteins, to investigate the microbial community of the oligotrophic northern Indian Ocean. Insignificant spatial variabilities of both genomic and proteomic compositions indicated a stable microbial community that was dominated by Prochlorococcus , Synechococcus , and SAR11. However, fine tuning of some metabolic functions that are mainly driven by salinity and temperature was observed. Intriguingly, a tuning divergence occurred between metabolic potential and activity in response to different environmental perturbations. Our results indicate that metabolic tuning is an important mechanism for sustaining the stability of microbial communities in oligotrophic oceans. In addition, integrated meta-omics provides a powerful tool to comprehensively understand microbial behavior and function in the ocean.

Road performance and microscopic action mechanism of low liquid limit silt solidified by AT curing agent - Jin Chang; Jian-Qing Jiang; Ming Lei; Shi-Lin Luo; Guang-Feng He; Jia-Yi Lin (Arabian Journal of Geosciences, 2022)

Ameliorating Effect of Umbilical Cord Mesenchymal Stem Cells in a Human Induced Pluripotent Stem Cell Model of Dravet Syndrome - Huifang Zhao; Shuai Li; Lang He; Feng Tang; Xiaobo Han; Weiyue Deng; Zuoxian Lin; Rongqi Huang; Zhiyuan Li (Molecular Neurobiology, 2022)

Beryllium-7 and Lead-210 are Associated with an Increase in the Arctic Oscillation: Evidence from Atmospheric Aerosols in a Remote Tropical Region in East Asia - Xiaoxia Chen; Wuhui Lin; Xianwen He; Liangliang Feng; Kuo-Ying Wang (Asia-Pacific Journal of Atmospheric Sciences, 2022)
The Arctic Oscillation (AO) accounts for a large fraction of recent decadal climate trends in Northern Hemisphere (NH) high latitudes. In East Asia, an elevated AO index (AOI) was associated with warmer temperatures in middle- to high-latitude regions, colder temperatures over low-latitude regions, and elevated ozone intrusion from the stratosphere. Elevated beryllium-7 ( 7 Be) is produced in the stratosphere. Few studies have discussed the relationship between 7 Be and the AO. Here, we identify the AO signature in 7 Be and lead (Pb)-210 observed at a tropical ambient monitoring site in Nanning (22.8°N, 108.5°E) during the December 2014–December 2017 period. Our results show that the 7 Be and 210 Pb concentrations are positively and significantly correlated with the AOI ( P 7 Be and 210 Pb are associated with an increase in the AOI, reflecting air masses originating from NH high latitudes and vertically from the high-latitude upper troposphere and lower stratosphere regions to tropical latitudes in East Asia. These results have been verified with ozonesonde data without seasonality and with two meteorological data sets. Our results are also confirmed by observational data over the Pacific regions. We conclude that the AO exerts impacts over the tropical regions in East Asia, and 7 Be can be used as a tracer to track the impacts of the AO.

New species and new record of Alternaria from onion leaf blight in Myanmar - Aye Aye Htun; Hai Feng Liu; Lin He; Zhen Zhou Xia; Sein Lai Lai Aung; Jian Xin Deng (Mycological Progress, 2022)

Bioactive compounds derived from the marine-derived fungus MCCC3A00951 and their influenza neuraminidase inhibition activity in vitro and in silico - Shun-Zhi Liu; Feng-Ming He; Yan-lin Bin; Chu-Fang Li; Bao-Ying Xie; Xi-Xiang Tang; Ying-Kun Qiu (Natural Product Research, 2021)

Selenium-Alleviated Testicular Toxicity by Modulating Inflammation, Heat Shock Response, and Autophagy Under Oxidative Stress in Lead-Treated Chickens - Size Wang; Lulu Hou; Min Wang; Rui Feng; Xu Lin; Shifeng Pan; Qian Zhao; He Huang (Biological Trace Element Research, 2021)

Dopaminergic Projection from Ventral Tegmental Area to Substantia Nigra Pars Reticulata Mediates Chronic Social Defeat Stress–Induced Hypolocomotion - Feng He; Pei Zhang; Qian Zhang; Guangjian Qi; Hongwei Cai; Tongxia Li; Ming Li; Jiazhen Lu; Jiaen Lin; Jie Ming; Bo Tian (Molecular Neurobiology, 2021)

Development and validation of gene-specific KASP markers for YrAS2388R conferring stripe rust resistance in wheat - Yanling Hu; Xuhui Huang; Fang Wang; Yu He; Lihua Feng; Bo Jiang; Ming Hao; Shunzong Ning; Zhongwei Yuan; Jiajie Wu; Lianquan Zhang; Bihua Wu; et al. (Euphytica, 2021)

Refractory organic compounds in coal chemical wastewater treatment by catalytic ozonation using Mn-Cu-Ce/Al2O3 - Kang-He Zhao; Yu-Long Ma; Feng Lin; Shao-Ying Ge; Li Zhu (Environmental Science and Pollution Research, 2021)

Phytoavailability, translocation and soil thresholds derivation of cadmium for food safety through soil-wheat (Triticum aestivum L.) system - Min Lu; Xuerui Cao; Qiang Lin; Bilal Hussain; Ying Feng; Zhenli He; Kyong Ju Kang; Xiaoe Yang (Environmental Science and Pollution Research, 2021)

Flavonoids from Artemisia rupestris and their synergistic antibacterial effects on drug-resistant Staphylococcus aureus - Jiang-Er Lan; Xiao-Jin Li; Xiao-Feng Zhu; Zhong-Lin Sun; Jian-Ming He; Mire Zloh; Simon Gibbons; Qing Mu (Natural Product Research, 2021)

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

miR-23b Attenuates LPS-Induced Inflammatory Responses in Acute Lung Injury via Inhibition of HDAC2 - Zhi-Feng Luo; Xiang-Hui Jiang; Huan Liu; Li-Yuan He; Xiong Luo; Fu-Chun Chen; Yu-Lin Tan (Biochemical Genetics, 2021)

Roles of FERONIA-like receptor genes in regulating grain size and quality in rice - Long Wang; Dandan Wang; Zhuhong Yang; Shun Jiang; Jianing Qu; Wei He; Zhenming Liu; Junjie Xing; Youchu Ma; Qinlu Lin; Feng Yu (Science China Life Sciences, 2021)

Simulating warmer and drier climate increases root production but decreases root decomposition in an alpine grassland on the Tibetan plateau - Huiying Liu; Li Lin; Hao Wang; Zhenhua Zhang; Zijian Shangguan; Xiaojuan Feng; Jin-Sheng He (Plant and Soil, 2021)

Transient receptor potential ankyrin 1 contributes to the ATP-elicited oxidative stress and inflammation in THP-1-derived macrophage - Chao Tian; Xiaobo Han; Lang He; Feng Tang; Rongqi Huang; Zuoxian Lin; Shuai Li; Sihao Deng; Junjie Xu; Hualin Huang; Huifang Zhao; Zhiyuan Li (Molecular and Cellular Biochemistry, 2020)

Long interpregnancy interval and adverse perinatal outcomes: A retrospective cohort study - Jing Lin; Han Liu; Dan-Dan Wu; Hong-Tao Hu; Hui-Hui Wang; Cheng-Liang Zhou; Xin-Mei Liu; Xiao-Jun Chen; Jian-Zhong Sheng; He-Feng Huang (Science China Life Sciences, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Hostaflavanol A, a new anti-inflammatory and antioxidant activities flavanol from the flowers of Hosta plantaginea - Li Yang; Yi-min Lin; Zhong-wei He; Ting-fang Zhang; Yu Li; Xiao-tong Xie; Yi-feng Wu; Jun-wei He (Medicinal Chemistry Research, 2020)

Stilbenoids from aerial parts of Dendrobium plicatile - Dan-Na Chen; Yu-Ye Wang; Wen-Jian Liu; Yue-Juan Chen; Ya-Ping Wu; Jing-Xian Wang; Feng He; Lin Jiang (Natural Product Research, 2020)

First report of tobacco rattle virus in hydrangea in China - Zhao-Lin Ji; Peng-Xiang Zhu; Gen-He He; Yong-Hui Liao; Feng Zhu (Journal of Plant Pathology, 2020)

Occurrence of chilli veinal mottle virus in Lycopersicon esculentum in Jiangxi Province in China - Yong-Hui Liao; Gen-He He; Zhao-Lin Ji; Feng Zhu (Journal of Plant Pathology, 2020)

Glutamate and aspartate alleviate testicular/epididymal oxidative stress by supporting antioxidant enzymes and immune defense systems in boars - Wenjie Tang; Jian Wu; Shunshun Jin; Liuqin He; Qinlu Lin; Feijun Luo; Xingguo He; Yanzhong Feng; Binsheng He; Pingping Bing; Tiejun Li; Yulong Yin (Science China Life Sciences, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Climate warming alters subsoil but not topsoil carbon dynamics in alpine grassland - Juan Jia; Zhenjiao Cao; Chengzhu Liu; Zhenhua Zhang; Li Lin; Yiyun Wang; Negar Haghipour; Lukas Wacker; Hongyan Bao; Thorston Dittmar; Myrna J. Simpson; Huan Yang; et al. (Global Change Biology, 2019)
Subsoil contains more than half of soil organic carbon (SOC) globally and is conventionally assumed to be relatively unresponsive to warming compared to the topsoil. Here, we show substantial changes in carbon allocation and dynamics of the subsoil but not topsoil in the Qinghai‐Tibetan alpine grasslands over 5 years of warming. Specifically, warming enhanced the accumulation of newly synthesized ( 14 C‐enriched) carbon in the subsoil slow‐cycling pool (silt‐clay fraction) but promoted the decomposition of plant‐derived lignin in the fast‐cycling pool (macroaggregates). These changes mirrored an accumulation of lipids and sugars at the expense of lignin in the warmed bulk subsoil, likely associated with shortened soil freezing period and a deepening root system. As warming is accompanied by deepening roots in a wide range of ecosystems, root‐driven accrual of slow‐cycling pool may represent an important and overlooked mechanism for a potential long‐term carbon sink at depth. Moreover, given the contrasting sensitivity of SOC dynamics at varied depths, warming studies focusing only on surface soils may vastly misrepresent shifts in ecosystem carbon storage under climate change.

Predominant effects of litter chemistry on lignin degradation in the early stage of leaf litter decomposition - Mei He; Rudong Zhao; Qiuxiang Tian; Lin Huang; Xinggang Wang; Feng Liu (Plant and Soil, 2019)

Seasonal Dynamics of Gastrointestinal Nematode Infections of Goats and Emergence of Ivermectin Resistance in Haemonchus contortus in Hubei Province, China - Wei Yuan; Ke Lu; Hao Li; Jinming Liu; Chuanchuan He; Jintao Feng; Xin Zhang; Yudan Mao; Yang Hong; Yu Zhou; Jun Lu; Yamei Jin; et al. (Acta Parasitologica, 2019)

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

QTL mapping for maize starch content and candidate gene prediction combined with co-expression network analysis - Feng Lin; Ling Zhou; Bing He; Xiaolin Zhang; Huixue Dai; Yiliang Qian; Long Ruan; Han Zhao (Theoretical and Applied Genetics, 2019)

Characterization of the Cd(II) and nitrate removal by bacterium Acinetobacter sp. SZ28 under different electron donor conditions - Jun Feng Su; Chun Yu Gao; Ting Lin Huang; Xue Chen Bai; Dong Hui Liang; Lei He (Environmental Science and Pollution Research, 2019)

Two Genes (ClS1 and ClF-box) Involved the Self-Incompatibility of ”Xiangshui” Lemon (Citrus limon (L.) Burm. f.) - Wei Lin; Shuwei Zhang; Feng Ding; Xinhua He; Cong Luo; Guixiang Huang; Minhphu Do; Qing Wang; Zaiyun Yang; Ling Su; Guibing Hu (Plant Molecular Biology Reporter, 2019)

Abundance of Early Embryonic Primordial Germ Cells Promotes Zebrafish Female Differentiation as Revealed by Lifetime Labeling of Germline - Ding Ye; Lin Zhu; Qifeng Zhang; Feng Xiong; Houpeng Wang; Xiaosi Wang; Mudan He; Zuoyan Zhu; Yonghua Sun (Marine Biotechnology, 2019)

Nitrogen addition does not reduce the role of spatial asynchrony in stabilising grassland communities - Yunhai Zhang; Jinchao Feng; Michel Loreau; Nianpeng He; Xingguo Han; Lin Jiang (Ecology Letters, 2019)
While nitrogen (N) amendment is known to affect the stability of ecological communities, whether this effect is scale‐dependent remains an open question. By conducting a field experiment in a temperate grassland, we found that both plant richness and temporal stability of community biomass increased with spatial scale, but N enrichment reduced richness and stability at the two scales considered. Reduced local‐scale stability under N enrichment arose from N‐induced reduction in population stability, which was partly attributable to the decline in local species richness, as well as reduction in asynchronous local population dynamics across species. Importantly, N enrichment did not alter spatial asynchrony among local communities, which provided similar spatial insurance effects at the larger scale, regardless of N enrichment levels. These results suggest that spatial variability among local communities, in addition to local diversity, may help stabilise ecosystems at larger spatial scales even in the face of anthropogenic environmental changes.

Activation of histamine H4 receptor suppresses the proliferation and invasion of esophageal squamous cell carcinoma via both metabolism and non-metabolism signaling pathways - Gong-Hao He; Jia-Qi Ding; Xin Zhang; Wen-Mang Xu; Xiao-Qian Lin; Mei-Jin Huang; Ju Feng; Ping Wang; Wen-Ke Cai (Journal of Molecular Medicine, 2018)

Rockburst occurrences and microseismicity in a longwall panel experiencing frequent rockbursts - Zhen-lei Li; Xue-qiu He; Lin-ming Dou; Gui-feng Wang (Geosciences Journal, 2018)

An improved Mahalanobis distance-based colour segmentation method for rural building recognition - Jia-li Xie; Yong-shu Li; Guo-lin Cai; Feng Wang; He-chao Li (Journal of Mountain Science, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Assessment of the baseline sensitivity and resistance risk of Colletotrichum acutatum to fludioxonil - Yangyang Gao; Lifei He; Wei Mu; Beixing Li; Jin Lin; Feng Liu (European Journal of Plant Pathology, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Sumoylation of SUVR2 contributes to its role in transcriptional gene silencing - Yu-Xi Luo; Yong-Feng Han; Qiu-Yuan Zhao; Jin-Lu Du; Kun Dou; Lin Li; She Chen; Xin-Jian He (Science China Life Sciences, 2018)

Correlation analyses revealed global microRNA–mRNA expression associations in human peripheral blood mononuclear cells - Lan Wang; Jiang Zhu; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Xiao-Wei Zhu; Wei Xia; Fang-Fei Xie; Pei He; Peng-Fei Bing; Ying-Hua Qiu; Xiang Lin; et al. (Molecular Genetics and Genomics, 2018)

Factors affecting palatability of four submerged macrophytes for grass carp Ctenopharyngodon idella - Jian Sun; Long Wang; Lin Ma; Fenli Min; Tao Huang; Yi Zhang; Zhenbin Wu; Feng He (Environmental Science and Pollution Research, 2017)

Sensitivity of Colletotrichum acutatum to six fungicides and reduction in incidence and severity of chili anthracnose using pyraclostrobin - Yang-Yang Gao; Li-Fei He; Bei-Xing Li; Wei Mu; Jin Lin; Feng Liu (Australasian Plant Pathology, 2017)

Ion Channel Genes and Epilepsy: Functional Alteration, Pathogenic Potential, and Mechanism of Epilepsy - Feng Wei; Li-Min Yan; Tao Su; Na He; Zhi-Jian Lin; Jie Wang; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao (Neuroscience Bulletin, 2017)

The In vitro/vivo Evaluation of Prepared Gastric Floating Tablets of Berberine Hydrochloride - Jun Ji; Xin He; Xiao-Lin Yang; Wen-Juan Du; Cheng-Long Cui; Ling Wang; Xue Wang; Chun-Feng Zhang; Chang-Run Guo (AAPS PharmSciTech, 2017)

Phenolic compounds from the stems of Flickingeria fimbriata - Ya-Ping Wu; Wen-Jian Liu; Wen-Jun Zhong; Yue-Juan Chen; Dan-Na Chen; Feng He; Lin Jiang (Natural Product Research, 2017)

The potential of fludioxonil for anthracnose control on China chili fruit - Yang-Yang Gao; Li-Fei He; Bei-Xing Li; Wei Mu; Jin Lin; Feng Liu (Phytoparasitica, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Quinone/hydroquinone meroterpenoids with antitubercular and cytotoxic activities produced by the sponge-derived fungus Gliomastix sp. ZSDS1-F7 - Wei-Jun He; Xiao-Jiang Zhou; Xiao-Chu Qin; Yong-Xin Mai; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Tianyu Zhang; Zheng-Chao Tu; Jun-Feng Wang; Yonghong Liu (Natural Product Research, 2017)

Effect of LA on the Growth and Development of the Main Organs in Female Mice - Xiuyuan He; Feng Lin; Yongtao Li; Yuxia Chen; Jing Li; Linlin Guo; Xuelei Han; Huan Song (Biological Trace Element Research, 2017)

Outlining a stepwise, multi-parameter debris flow monitoring and warning system: an example of application in Aizi Valley, China - Ning-sheng Chen; Javed Iqbal Tanoli; Gui-sheng Hu; Feng-niang Wang; Cheng-lin Yang; Hai-tao Ding; Na He; Tao Wang (Journal of Mountain Science, 2016)

A new tigliane-type diterpene from Euphorbia dracunculoides Lam - Lin-Feng Dai; Qian Liang; Tie Liu; Ming-Yu He; Ping Zhao; Wen-Hui Xu (Natural Product Research, 2016)

Magnolol pretreatment attenuates heat stress-induced IEC-6 cell injury - Chen Mei; Sha-sha He; Peng Yin; Lei Xu; Ya-ran Shi; Xiao-hong Yu; An Lyu; Feng-hua Liu; Lin-shu Jiang (Journal of Zhejiang University-SCIENCE B, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

A new method of deep carbonate lithology identification at the Tadong uplift in the eastern section of the Tarim Basin - Jingyan Liu; Qian Chang; Changsong Lin; Junlong Zhang; Feng He; Shiqiang Xia (Arabian Journal of Geosciences, 2016)

Effect of combination of nerve fragments with nerve growth factor in autologous epineurium small gap coaptation on peripheral nerve injury repair - Bo Feng; Hua Ma; He Hu; Lan Zhang; Zhi Zhang; Youming Pang; Yongjun Wang; Kecheng Niu; Ligong Lin (Cell and Tissue Banking, 2015)

Adenovirus-mediated osteoprotegerin ameliorates cartilage destruction by inhibiting proteoglycan loss and chondrocyte apoptosis in rats with collagen-induced arthritis - Zhi-yun Feng; Zhen-nian He; Bin Zhang; Yi-qiao Li; Jian Guo; Yuan-lin Xu; Ming-yuan Han; Zhong Chen (Cell and Tissue Research, 2015)

Distribution and phylogenetic analysis of Culex flavivirus in mosquitoes in China - Wenkai Liang; Xiaoxia He; Guifang Liu; Shaobai Zhang; Shihong Fu; Min Wang; Weixin Chen; Ying He; Xiaoyan Tao; Hongyue Jiang; Xiaojuan Lin; Xiaoyan Gao; et al. (Archives of Virology, 2015)

Effects of flow speed and circulation interval on water quality and zooplankton in a pond–ditch circulation system - Lin Ma; Feng He; Jian Sun; Tao Huang; Dong Xu; Yi Zhang; Zhenbin Wu (Environmental Science and Pollution Research, 2015)

Identification of a novel compound heterozygous mutation in PTPRQ in a DFNB84 family with prelingual sensorineural hearing impairment - Qing Sang; Honglin Mei; Ahan Kuermanhan; Ruizhi Feng; Luo Guo; Ronggui Qu; Yao Xu; Huawei Li; Li Jin; Lin He; Lei Wang (Molecular Genetics and Genomics, 2015)

Rapid emergence of a PB2-E627K substitution confers a virulent phenotype to an H9N2 avian influenza virus during adaption in mice - Xiaoyu Sang; Airong Wang; Tongjie Chai; Xijun He; Jie Ding; Xiaolong Gao; Yuanguo Li; Kun Zhang; Zhiguang Ren; Lin Li; Zhijun Yu; Tiecheng Wang; et al. (Archives of Virology, 2015)

Association between the CYP1A2 polymorphisms and risk of cancer: a meta-analysis - Wen-Xia Sun; Ying-Hua Chen; Zhi-Zhong Liu; Jian-Jun Xie; Wei Wang; Ya-Ping Du; Yu Chen; Xu-Liang Shen; Xiao-Feng He; Li-Xia Wu; Wu Wei; Lin Zhang (Molecular Genetics and Genomics, 2015)

Bacillus vanillea sp. nov., Isolated from the Cured Vanilla Bean - Yong-gan Chen; Feng-lin Gu; Ji-hua Li; Fei Xu; Shu-zhen He; Yi-ming Fang (Current Microbiology, 2015)

Phylogenetic analysis of STK gene family and Usp domain in maize - Ting Zhou; Mingxia Fan; Muhammad Irfan; He Wang; Dongxu Wang; Lin Wang; Chunyu Zhang; Lin Feng (Molecular Biology Reports, 2014)

Fibroblast Growth Factor 4 Is Required but not Sufficient for the Astrocyte Dedifferentiation - Guo-Dong Feng; Bao-Rong He; Fan Lu; Lin-Hong Liu; Lingling Zhang; Bo Chen; Zu-Ping He; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

Trehalose Alleviates PC12 Neuronal Death Mediated by Lipopolysaccharide-Stimulated BV-2 Cells via Inhibiting Nuclear Transcription Factor NF-κB and AP-1 Activation - Qing He; Ying Wang; Wei Lin; Qiong Zhang; Jue Zhao; Feng-Tao Liu; Yi-Lin Tang; Bao-guo Xiao; Jian Wang (Neurotoxicity Research, 2014)

Intracellular Ca2+ Overload Induced by Extracellular Ca2+ Entry Plays an Important Role in Acute Heart Dysfunction by Tentacle Extract from the Jellyfish Cyanea capillata - Lin Zhang; Qian He; Qianqian Wang; Bo Zhang; Beilei Wang; Feng Xu; Tao Wang; Liang Xiao; Liming Zhang (Cardiovascular Toxicology, 2014)

Polymorphisms of pentanucleotide repeats (tttta)n in the promoter of CYP11A1 and their relationships to polycystic ovary syndrome (PCOS) risk: a meta-analysis - Min Yu; Ruizhi Feng; Xiaoxi Sun; Haojue Wang; Huan Wang; Qing Sang; Li Jin; Lin He; Lei Wang (Molecular Biology Reports, 2014)

The Chilli Veinal Mottle Virus Regulates Expression of the Tobacco Mosaic Virus Resistance Gene N and Jasmonic Acid/Ethylene Signaling Is Essential for Systemic Resistance Against Chilli Veinal Mottle Virus in Tobacco - Feng Zhu; De-Hui Xi; Xing-Guang Deng; Xing-Ji Peng; He Tang; Ying-Juan Chen; Wei Jian; Hong Feng; Hong-Hui Lin (Plant Molecular Biology Reporter, 2014)

Genetic variation at 8q24, family history of cancer, and upper gastrointestinal cancers in a Chinese population - Heather P. Tarleton; Shen-Chih Chang; Sungshim Lani Park; Lin Cai; Baoguo Ding; Na He; Shehnaz K. Hussain; Qingwu Jiang; Li-Na Mu; Jianyu Rao; Hua Wang; Nai-Chieh Y. You; et al. (Familial Cancer, 2014)

Mapping Quantitative Trait Loci for Omega-3 Fatty Acids in Asian Seabass - Jun Hong Xia; Grace Lin; Xiaoping He; Bu Yunping; Peng Liu; Feng Liu; Fei Sun; Rongjian Tu; Gen Hua Yue (Marine Biotechnology, 2014)

JNK Is Necessary for Oligodendrocyte Precursor Cell Proliferation Induced by the Conditioned Medium from B104 Neuroblastoma Cells - Jing-Xing Zhang; Yi-Fan Feng; Qi Qi; Lin Shen; Rui Wang; Jian-Sheng Zhou; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2014)

WNT10A variants are associated with non-syndromic tooth agenesis in the general population - Shujuan Song; Ruiying Zhao; Huiying He; Jin Zhang; Hailan Feng; Liyun Lin (Human Genetics, 2014)

Fumigant activity of Illicium verum fruit extracts and their effects on the acetylcholinesterase and glutathione S-transferase activities in adult Sitophilus zeamais - Shi-Guang Li; Mao-Ye Li; Yan-Zhang Huang; Ri-Mao Hua; Hua-Feng Lin; Yu-Jie He; Lin-Lin Wei; Zhu-Qin Liu (Journal of Pest Science, 2013)

Selenium Deficiency Is Associated with Endoplasmic Reticulum Stress in a Rat Model of Cardiac Malfunction - Su-Qin Wang; Xiao-Lin Niu; Zhong-Wei Liu; Yan-He Zhu; Deng-Feng Gao (Biological Trace Element Research, 2013)

The roles of two transcription factors, ABI4 and CBFA, in ABA and plastid signalling and stress responses - Zhong-Wei Zhang; Ling-Yang Feng; Jian Cheng; He Tang; Fei Xu; Feng Zhu; Zhong-Yi Zhao; Ming Yuan; Yang-Er Chen; Jian-Hui Wang; Shu Yuan; Hong-Hui Lin (Plant Molecular Biology, 2013)

Soil microbial mechanisms of Stevia rebaudiana (Bertoni) residue returning increasing crop yield and quality - Jiangbing Xu; Youzhi Feng; Yiming Wang; Junhua Wang; Xinhua He; Xiangui Lin (Biology and Fertility of Soils, 2013)

Genetic analysis and location of gene for resistance to stripe rust in wheat international differential host Strubes Dickkopf - FENG JING; XU JIAO-JIAO; LIN RIN-MING; HE YUE-QIU; XU SHI-CHANG (Journal of Genetics, 2013)

Iron Overload Inhibits Osteoblast Biological Activity Through Oxidative Stress - Yin-Feng He; Yong Ma; Chao Gao; Guo-yang Zhao; Lin-Lin Zhang; Guang-Fei Li; Yun-Zhi Pan; Kai Li; You-Jia Xu (Biological Trace Element Research, 2013)

Common genetic variation in CYP1B1 is associated with concentrations of T4, FT3 and FT4 in the sera of polycystic ovary syndrome patients - Shien Zou; Qing Sang; Huan Wang; Ruizhi Feng; Qiaoli Li; Xinzhi Zhao; Qinghe Xing; Li Jin; Lin He; Lei Wang (Molecular Biology Reports, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Effect of Sulfate Availability on the Isotopic Signature of Reduced Sulfurous Compounds in the Sediments of a Subtropical Estuary - Lan-Feng Fan; Saulwood Lin; Wei-Gang He; Kuo-Ming Huang; Chang-Po Chen; Hwey-Lian Hsieh (Wetlands, 2012)

NMDA receptor glycine modulatory site in the ventral tegmental area regulates the acquisition, retrieval, and reconsolidation of cocaine reward memory - Shuang-jiang Zhou; Li-fen Xue; Xue-yi Wang; Wen-gao Jiang; Yan-xue Xue; Jian-feng Liu; Yin-yin He; Yi-xiao Luo; Lin Lu (Psychopharmacology, 2012)

SIRT1 is required for long-term growth of human mesenchymal stem cells - Hong-Feng Yuan; Chao Zhai; Xin-Long Yan; Dan-Dan Zhao; Jing-Xue Wang; Quan Zeng; Lin Chen; Xue Nan; Li-Juan He; Si-Ting Li; Wen Yue; Xue-Tao Pei (Journal of Molecular Medicine, 2012)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

The cyclophosphamide metabolite, acrolein, induces cytoskeletal changes and oxidative stress in Sertoli cells - Feng Liu; Xu-Liang Li; Tao Lin; Da-Wei He; Guang-Hui Wei; Jun-Hong Liu; Lu-Sheng Li (Molecular Biology Reports, 2012)

Rapid change of AM fungal community in a rain-fed wheat field with short-term plastic film mulching practice - Yongjun Liu; Lin Mao; Xinhua He; Gang Cheng; Xiaojun Ma; Lizhe An; Huyuan Feng (Mycorrhiza, 2012)

The impact of iron oxide magnetic nanoparticles on the soil bacterial community - Shiying He; Youzhi Feng; Hongxuan Ren; Yu Zhang; Ning Gu; Xiangui Lin (Journal of Soils and Sediments, 2011)

Identification of three immediate-early genes of white spot syndrome virus - Fanyu Lin; He Huang; Limei Xu; Fang Li; Feng Yang (Archives of Virology, 2011)

Over-expression of mango (Mangifera indica L.) MiARF2 inhibits root and hypocotyl growth of Arabidopsis - Bei Wu; Yun-He Li; Jian-Yong Wu; Qi-Zhu Chen; Xia Huang; Yun-Feng Chen; Xue-Lin Huang (Molecular Biology Reports, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Asialoglycoprotein receptor interacts with the preS1 domain of hepatitis B virus in vivo and in vitro - Xi Zhang; Shu-mei Lin; Tian-yan Chen; Min Liu; Feng Ye; Yun-ru Chen; Lei Shi; Ying-li He; Lie-xiu Wu; Shu-qin Zheng; Ying-ren Zhao; Shu-lin Zhang (Archives of Virology, 2011)

Hepatitis B virus infection and replication in primary cultured human granulosa cells - Yan Jin; Feng Ye; Juanzi Shi; Hongtao Qiu; Yingren Zhao; Shumei Lin; Tianyan Chen; Min Liu; Yingli He; Shulin Zhang (Archives of Virology, 2011)

Th17 promotes acute rejection following liver transplantation in rats - Xiao-jun Xie; Yu-fu Ye; Lin Zhou; Hai-yang Xie; Guo-ping Jiang; Xiao-wen Feng; Yong He; Qin-fen Xie; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Erratum to: AtCPK6, a functionally redundant and positive regulator involved in salt/drought stress tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xiao-Fen Jin; Feng Gao; Xiao-Yan Fu; Xi-Lin Hou; Quan-Hong Yao (Planta, 2010)

Predicting subcellular location of proteins using integrated-algorithm method - Yu-Dong Cai; Lin Lu; Lei Chen; Jian-Feng He (Molecular Diversity, 2010)

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)

AtCPK6, a functionally redundant and positive regulator involved in salt/drought stress tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xiao-Fen Jin; Feng Gao; Xiao-Yan Fu; Xi-Lin Hou; Quan-Hong Yao (Planta, 2010)

Platinum-group minerals and tellurides from the PGE-bearing Xinjie layered intrusion in the Emeishan Large Igneous Province, SW China - Wei-Guang Zhu; Hong Zhong; Rui-Zhong Hu; Bing-Guang Liu; De-Feng He; Xie-Yan Song; Hai-Lin Deng (Mineralogy and Petrology, 2010)

Protein sumoylation sites prediction based on two-stage feature selection - Lin Lu; Xiao-He Shi; Su-Jun Li; Zhi-Qun Xie; Yong-Li Feng; Wen-Cong Lu; Yi-Xue Li; Haipeng Li; Yu-Dong Cai (Molecular Diversity, 2010)

Gene mapping and expression analysis of a novel mutantreproduce organs absent (roa) in rice - Nan Wang; Xian-Chun Sang; Yun-Feng Li; Ying-Hua Ling; Fang-Ming Zhao; Zheng-Lin Yang; Guang-Hua He (Genes & Genomics, 2009)

Polymorphisms within promoter of Japanese flounder (Paralichthys olivaceus) ovary cytochrome P450-c19 (CYP19a) gene associated with reproductive traits - Feng He; Hai Shen Wen; Shuang Lin Dong; Bao Shi; Cai Fang Chen; Lian Shun Wang; Jun Yao; Xing Jiang Mu; Yu Guo Zhou (Fish Physiology and Biochemistry, 2009)

Salicylic acid activates artemisinin biosynthesis in Artemisia annua L. - Gao-Bin Pu; Dong-Ming Ma; Jian-Lin Chen; Lan-Qing Ma; Hong Wang; Guo-Feng Li; He-Chun Ye; Ben-Ye Liu (Plant Cell Reports, 2009)

Establishment of cell lines using a doxycycline-inducible gene expression system to regulate expression of hepatitis B virus X protein - Hong Tang; Li Liu; Feng-Jun Liu; En-Qiang Chen; Seishi Murakami; Yong Lin; Fang He; Tao-You Zhou; Fei-Jun Huang (Archives of Virology, 2009)

Proteome alteration of U251 human astrocytoma cell after inhibiting retinoic acid synthesis - Ming Zhang; Chunling Wan; Baohu Ji; Zhao Zhang; Hui Zhu; Nan Tian; Yujuan La; Ke Huang; Lei Jiang; Guang He; Linhan Gao; Xinzhi Zhao; et al. (Molecular and Cellular Biochemistry, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

The distribution of HBV genotypes and clinical significance in familial clustering in an infected population with unfavorable prognosis - Jinfeng Liu; Yongqin Li; Tianyan Chen; Yuan Yang; Ke Wang; Yingli He; Qian Yang; Feng Ye; Yan Jin; Ting Qiu; Shumei Lin; Min Liu; et al. (Archives of Virology, 2008)

Positive association between OLIG2 and schizophrenia in the Chinese Han population - Ke Huang; Wei Tang; Ruqi Tang; Zhao Xu; Zhangdong He; Zhiqiang Li; Yifeng Xu; Xingwang Li; Guang He; Guoying Feng; Lin He; YongYong Shi (Human Genetics, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A locus for familial generalized lentiginosis without systemic involvement maps to chromosome 4q21.1–q22.3 - Qinghe Xing; Xiangdong Chen; Mingtai Wang; Wenjie Bai; Xin Peng; Rui Gao; Shengnan Wu; Xueqing Qian; Wei Qin; Jianjun Gao; Guoyin Feng; Lin He (Human Genetics, 2005)

Mapping QTLs of traits contributing to yield and analysis of genetic effects in tetraploid cotton - Dao-Hua He; Zhong-Xu Lin; Xian-Long Zhang; Yi-Chun Nie; Xiao-Ping Guo; Chun-Da Feng; James McD. Stewart (Euphytica, 2005)

CYP2C19 genotype and S-mephenytoin 4′-hydroxylation phenotype in a Chinese Dai population - Nan He; Feng-Xiang Yan; Song-Lin Huang; Wei Wang; Zhou-Sheng Xiao; Zhao-Qian Liu; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)